Packaging material
By using a laminated base film with a gas barrier layer and a heat-sealing resin layer with excellent linear cutting properties in the packaging material, the problem of difficulty in realizing single materialization and taking into account multiple properties in the prior art is solved, and an environmentally friendly, convenient and multifunctional packaging material is achieved.
Patent Information
- Application Number
- CN202380065309.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to achieve single materialization in packaging materials such as food and medicine, while taking into account gas barrier, cutting and hardness, making it difficult to design environmentally friendly and convenient packaging materials.
By making a laminated base film with a gas barrier layer and controlling its heating elongation, a heat sealing resin layer with excellent linear cutting properties and strong stiffness can be formed to form an environmentally friendly and convenient packaging material.
It realizes the environmental protection and convenience of packaging materials, and at the same time it has gas barrier, cutting and hard feeling, meeting the needs of versatility.
Smart Images

Figure BDA0005306380690000461 
Figure BDA0005306380690000471 
Figure BDA0005306380690000481
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated packaging material used in the field of packaging of food, medicine, industrial products, etc. More specifically, it relates to an environmentally friendly laminated packaging material having excellent gas barrier properties, linear cutting properties, and stiffness and having convenience. Background Art
[0002] In recent years, countries around the world, led by Europe, have been strengthening their control over reducing the use of disposable plastics. Against this backdrop, there is an increase in international awareness of resource recycling and a worsening of garbage problems in emerging countries. Therefore, for plastic packaging materials for food, medicine, etc., environmentally friendly products are also required from the perspective of 3R (Recycle, Reuse, Reduce).
[0003] As one of the possibilities for producing the above-mentioned environmentally friendly packaging materials, the packaging materials are actively studied to be formed of the same raw material that can be recycled, that is, to be made of a single material. As raw materials for achieving single material, for example, polyester-based or polyolefin-based materials are studied.
[0004] The current situation is that while seeking packaging materials with low environmental burden as mentioned above, in order to achieve convenience, the characteristics required of the packaging materials themselves are gradually becoming more multifunctional. In particular, for boiling / steaming soft bags that can be used in microwave ovens without using aluminum foil, the bag's gas barrier, heat resistance, toughness (bag breakage resistance, pinhole resistance), high sealing, straight-line cutting, and self-supporting properties (stiffness) are required in one packaging bag. In order to achieve this, different raw materials with different functions need to be pasted together, usually presenting a structure of at least three layers obtained by dry laminating a vapor-deposited polyester film on the outside of the bag with the help of an adhesive, dry laminating a polyamide film in the middle layer, and dry laminating a polyolefin-based heat-sealing resin on the inside (content side). If it is this structure, there is a possibility that the target performance can be achieved, but because it is the pasting of different raw materials, there is a problem of poor recyclability and it cannot be said to be the aforementioned environmentally friendly packaging material.
[0005] In view of these points, research has been conducted on whether it is possible to design an ideal packaging material having the multifunctionality of the bag described above using the same raw material that can be made into a single material.
[0006] In the design of polyester-based single-material packaging materials, as an alternative to the conventional polyolefin-based sealants, a polyester-based sealant with improved low adsorption and heat resistance is disclosed (for example, see Patent Document 1). The sealant of Patent Document 1 satisfies both heat sealing and heat resistance by dividing into a layer having heat sealing properties and other layers, and separately controlling the raw material composition of these layers. However, regarding heat sealing properties, there is a problem of inferior sealing strength compared to polyolefin-based sealants, and in terms of heat resistance, the current situation is that it cannot withstand harsh treatments such as boiling and retorting.
[0007] On the other hand, in the design of polyolefin-based single-material packaging materials, polyolefin-based heat-sealing resins can be used as sealants, which have the advantage of ensuring sufficient heat-sealing properties compared to the aforementioned polyester-based sealants. The sealant needs to have a certain degree of thickness due to the necessity of exhibiting sufficient sealing properties, and its proportion in the package body is large. This has also become the main reason for promoting the design of polyolefin-based single-material packaging materials. On the other hand, polyolefin-based packaging materials have poor gas barrier properties compared to conventional packaging with barrier properties. Although polypropylene film has water vapor barrier properties, there are problems such as that it is not sufficient compared to transparent inorganic vapor-deposited polyester films that are generally regarded as having excellent water vapor barrier properties, and that the oxygen barrier properties are very poor.
[0008] In response to this, a film obtained by laminating a polymer resin composition generally said to have high oxygen barrier properties, such as polyvinyl alcohol, ethylene vinyl alcohol copolymer, polyvinylidene chloride resin, and polyacrylonitrile, on a polypropylene film is used (for example, refer to Patent Documents 2 to 4). However, the humidity dependence of the gas barrier coating film formed using the polymer resin composition of the above-mentioned polyvinyl alcohol and ethylene vinyl alcohol copolymer is large, so a decrease in gas barrier properties is observed under high humidity, and it does not have moisture and heat resistance that can withstand sterilization treatments such as boiling and steaming. In addition, polyvinylidene chloride resin and polyacrylonitrile have low humidity dependence, but there are problems such as insufficient barrier values in absolute values and high risk of generating harmful substances during disposal / incineration. Furthermore, there is the following problem: the heat resistance of the polypropylene film used is insufficient, and the film expands and contracts due to the heat applied during coating, printing, lamination, and sterilization, thereby causing wrinkles in appearance and reduced performance.
[0009] Regarding improving the gas barrier properties of polypropylene films, attempts have been made to achieve stable gas barrier properties without humidity dependence by laminating inorganic films (e.g., Patent Document 5). However, there are also problems such as the absolute value of gas barrier properties (especially oxygen barrier properties) of conventional polyester vapor-deposited films being poor and not resistant to physical damage compared to the aforementioned coating-type barrier films. In addition, barrier materials obtained by vapor-depositing polyolefin-based sealants have also been studied (e.g., Patent Document 6), and although they exhibit water vapor barrier properties, they have problems such as insufficient oxygen barrier properties.
[0010] When applying polyolefin-based single-material packaging materials to boiling / retorting soft bags, the demand for which has been increasing in recent years due to the social background, it is necessary to consider the cutting properties of the bag in addition to the above-mentioned barrier performance issues. Generally speaking, when taking out food contents from a soft bag, the bag is often cut by hand from the cut portion, so-called cut portion, made at the sealing portion around the bag. However, when using a conventional laminate, it may not be possible to tear the bag parallel to one side of the bag, usually in the horizontal direction, and the bag may be opened obliquely or the tearing direction of the laminate on the surface and back of the bag may be reversed, so-called bad separation, which may make it difficult to take out the food contents, and the food contents may stain hands and clothes, or cause burns when the contents are heated.
[0011] The reason why it is difficult to tear the packaging bag parallel to one side of the packaging bag is that the base film used in the laminate is deformed, that is, the molecular orientation axis of the base film is not parallel to one side of the packaging body.
[0012] This problem will not occur if the molecular orientation axis of the substrate film can be made the same as the tearing direction of the packaging bag. The molecular orientation axis of the central part in the width direction of the manufactured wide-width stretched film is consistent with the traveling direction of the film, and can be torn parallel to one side of the packaging bag. However, at the ends in the width direction of the film, the molecular orientation axis is tilted, and the tearing direction of the packaging bag is tilted. It is not realistic to completely avoid the use of substrate films obtained from the ends in the width direction of the film for supply, and as the production speed of the substrate film increases and the width increases, there is a tendency for the degree of deformation to increase further than before. In response to this, attempts have been made to solve this problem by improving the polyolefin-based heat-sealing resin laminated with the substrate film.
[0013] As a heat-seal resin with improved cutting properties, a film obtained by uniaxially stretching a polyolefin resin sheet containing an ethylene-propylene block copolymer and an ethylene-propylene copolymer at a ratio of 3.0 or less is known (for example, see Examples 1 and 2 of Patent Document 7). However, there is still room for improvement in tear strength, and there is a problem that poor separation is easily caused. Furthermore, using a film of a different raw material other than polyolefin as the base layer and using aluminum foil as the barrier layer cannot be recycled.
[0014] Furthermore, when applying polyolefin-based single-material packaging materials in boiling / retorting soft bags, in addition to the aforementioned issues of barrier performance and cuttability, the self-supporting property of the bag must also be considered. In the past, retorting soft bags formed of different raw materials were laminated with biaxially stretched polyester films and biaxially stretched nylon films with strong stiffness in order to make the bags self-supporting. In contrast, olefin-based films are generally less rigid, so it may not be possible to ensure the stiffness required for the self-support of the bag.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent Application Publication No. 2017-165059
[0018] Patent Document 2: Japanese Patent Application Publication No. 2000-52501
[0019] Patent Document 3: Japanese Patent Application Laid-Open No. 4-359033
[0020] Patent Document 4: Japanese Patent Application Publication No. 2003-231221
[0021] Patent Document 5: International Publication No. 2017 / 221781
[0022] Patent Document 6: Japanese Patent No. 3318479
[0023] Patent Document 7: Japanese Patent No. 5790497 Summary of the invention
[0024] Problem that the invention aims to solve
[0025] In the above patent documents, it is difficult to realize a single material packaging material, and it is difficult to achieve a balance between various properties required of the packaging material, especially gas barrier properties, cutting properties, and stiffness, and it is impossible to design an environmentally friendly and convenient packaging material.
[0026] The present invention was made against the background of the above-mentioned problems in the prior art. That is, the subject of the present invention is to provide a packaging material that can form a laminated structure composed of resin types with low environmental burden and has all three properties required for packaging materials, namely, gas barrier properties, cutting properties, and stiffness.
[0027] Solutions for solving problems
[0028] The present inventors have discovered that by making a laminated film in which a specified gas barrier layer that meets the required performance is laminated on a base film, the gas barrier performance can be greatly improved. Furthermore, by controlling the heating elongation of the aforementioned laminated film, heat resistance for various processing and sterilization treatments can be ensured. Finally, by pasting a resin layer having excellent straight-line cutting properties and a strong stiffness as a heat-sealable resin film to the aforementioned base film, an environmentally friendly and convenient packaging material can be provided, thereby completing the present invention.
[0029] That is, the present invention includes the following technical solutions.
[0030] 1. A packaging material comprising a heat-sealable resin film and at least one substrate film having a polyolefin resin as a constituent component,
[0031] At least one of the substrate films is a laminated substrate film having a gas barrier layer,
[0032] At least one of the substrate films peeled off from the packaging material has a heating elongation at 130° C. measured by a thermomechanical analyzer in both the MD direction and the TD direction of 6% or less,
[0033] The straight-line cutting property of the packaging material is less than 10 mm in the MD direction or the TD direction, and the ring stiffness is more than 140 mN / 25 mm.
[0034] The oxygen permeability of the packaging material under 23°C×65%RH environment is 60ml / m 2 ·d·MPa or less.
[0035] 2. The packaging material according to 1., characterized in that the heat-sealable resin film comprises a propylene-α-olefin random copolymer and further comprises at least one component selected from the group consisting of an ethylene-propylene copolymer elastomer, an ethylene-butene copolymer elastomer, and a propylene-butene copolymer elastomer.
[0036] 3. The packaging material according to 1. or 2., characterized in that the gas barrier layer is an inorganic thin film layer formed of a material selected from the group consisting of aluminum, aluminum oxide, silicon oxide, and a composite oxide of silicon oxide and aluminum oxide.
[0037] 4. The packaging material according to any one of 1. to 3., wherein the gas barrier layer is a covering layer containing a resin selected from the group consisting of polyvinyl alcohol resins, polyester resins, and polyurethane resins as a constituent component.
[0038] 5. The packaging material according to any one of 1. to 4., wherein an anchor coating layer is laminated between the base film and the gas barrier layer.
[0039] 6. The packaging material according to any one of 1. to 5., wherein a protective layer is laminated on the gas barrier layer.
[0040] 7. The packaging material according to any one of 1. to 6., wherein two or more of the base films are used.
[0041] 8. The packaging material according to any one of 1. to 7., wherein the polyolefin resin constituting the base film contains 1% by mass or more and 25% by mass or less of a plant-derived polyethylene resin.
[0042] 9. The packaging material according to any one of 1. to 8., characterized in that it is used for boiling or steaming.
[0043] 10. The packaging material according to any one of 1. to 8., characterized in that it is used for heating in a microwave oven.
[0044] 11. A packaging bag, which is formed using the packaging material according to any one of 1. to 10. above.
[0045] 12. A package body, which is obtained by packaging an object using the packaging material according to any one of 1. to 10. above or the packaging bag according to 11. above.
[0046] Effects of the Invention
[0047] The present inventors have been able to provide an environmentally friendly packaging material that has the necessary properties required of a packaging material, such as barrier properties, cuttability, and stiffness, based on the above-described technology. DETAILED DESCRIPTION
[0048] The packaging material of the present invention is characterized in that it comprises a heat-sealable resin film and at least one substrate film having a polyolefin resin as a constituent component, at least one of the substrate films is a laminated substrate film having a gas barrier layer, at least one of the substrate films peeled off from the packaging material has a heating elongation at 130° C. measured by a thermomechanical analyzer in both the MD direction and the TD direction of 6% or less, the linear cutting property of the packaging material is 10 mm or less in the MD direction or the TD direction, and the ring stiffness is 140 mN / 25 mm or more, and the oxygen permeability of the packaging material under a 23° C.×65% RH environment is 60 ml / m 2 It should be noted that the aforementioned substrate film preferably has a polyolefin resin as a main constituent, and the aforementioned "main constituent" means that it contains 50% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more in the constituents.
[0049] Hereinafter, the present invention will be described in detail.
[0050] [Base film]
[0051] The packaging material of the present invention is provided with a substrate film having a polyolefin resin as a constituent component. The substrate film is preferably a substrate film having a polypropylene resin as a main constituent component (hereinafter referred to as a polypropylene resin film), and is more preferably a stretched film. The polypropylene resin stretched film used as the substrate film in the present invention is preferably a biaxially stretched film. As a biaxially stretched polypropylene resin film, a known biaxially stretched polypropylene resin film can be used, and its raw materials, mixing ratio, etc. are not particularly limited. For example, in addition to a polypropylene homopolymer (propylene homopolymer), it can be a random copolymer, a block copolymer, etc. having propylene as the main component and being selected from 1 or more of α-olefins such as ethylene, butene, pentene, and hexene, or a mixture obtained by mixing more than two of these polymers. In addition, for the purpose of modifying physical properties, known additives such as antioxidants, antistatic agents, and plasticizers can be added, for example, petroleum resins, terpene resins, etc. can be added.
[0052] In the present invention, as the polypropylene resin constituting the substrate film, it is preferably a propylene homopolymer substantially free of comonomers other than propylene, and even if a comonomer is included, the comonomer amount is preferably less than 0.5 mol% in all monomers constituting the polypropylene resin. The upper limit of the comonomer amount is more preferably 0.3 mol%, and further preferably 0.1 mol%. If it is the above range, the crystallinity is improved, the dimensional change at high temperature becomes smaller, and the heat resistance is improved. It should be noted that, within the range of not significantly reducing the crystallinity, if it is a trace amount, the comonomer can be included.
[0053] In addition, the biaxially stretched polypropylene resin film used in the present invention can be a monolayer film or a laminated film, for example, a laminated film comprising a substrate layer and more than one surface layer can be made, preferably a laminated film having a surface layer on both sides of the substrate layer (surface layer / substrate layer / surface layer). Wherein, in order to achieve the purpose of the present invention, preferably a laminated film, the type of laminate, the number of layers, the lamination method, etc. are not particularly limited, and can be arbitrarily selected from known methods, but preferably by controlling the surface roughness and softness of the substrate film surface (that is, by making a laminated film of surface layer / substrate layer / surface layer), thereby improving the bonding strength of lamination strength, coating agent, etc.
[0054] In the present invention, as a means to improve the lamination strength of the substrate film and the interfacial bonding strength with the inorganic film layer, coating agent, etc., a mixture of two or more polypropylene resins with different melt flow rates (MFR) can be used as the polypropylene resin constituting the surface layer of the substrate film.
[0055] It is speculated that when the difference in melt flow rate (MFR) of two or more polypropylene resins in the mixture of polypropylene resins is small, the crystallization rate and crystallinity of each polypropylene resin will not be significantly different, and it is easy to generate tiny unevenness on the surface. However, when manufacturing a film, if the cooling rate of the unstretched sheet is slow, the surface unevenness caused by spherulites becomes larger, and when the longitudinal stretching or transverse stretching is performed, the stretching temperature is too high, and the surface unevenness tends to become larger, so it is necessary to pay attention.
[0056] As various polypropylene resins, polypropylene homopolymers containing no copolymerization components and polypropylene resins obtained by copolymerizing ethylene and / or alpha-olefins with carbon atoms of 4 or more with 5.0 mol% or less can be used. The copolymerization components of the copolymerized polypropylene resin are preferably 4.0 mol% or less, more preferably 3.5 mol% or less. The copolymerization components of the copolymerized polypropylene resin are preferably 1.0 mol% or more, more preferably 1.5 mol% or more, further preferably 2.0 mol% or more, and particularly preferably 2.5 mol% or more. As alpha-olefins with carbon atoms of 4 or more, 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. can be listed. In addition, as other copolymerization components, polar maleic acid, etc. can be used.
[0057] From a practical aspect, the lower limit of the xylene soluble component of the polypropylene resin constituting the substrate film is preferably 0.1% by mass. The upper limit of the xylene soluble component is preferably 7% by mass, more preferably 6% by mass, and further preferably 5% by mass. If it is within the above range, the crystallinity is improved, the dimensional change during heating becomes smaller, and the heat resistance is improved, so it is preferred.
[0058] In the present invention, the lower limit of the melt flow rate (MFR) (230°C, 2.16kgf) of the polypropylene resin is preferably 0.5g / 10 minutes. The lower limit of MFR is more preferably 1.0g / 10 minutes, further preferably 2.0g / 10 minutes, particularly preferably 4.0g / 10 minutes, and most preferably 6.0g / 10 minutes. If it is within the above range, the mechanical burden is small, and it is easy to extrude and stretch. The upper limit of MFR is preferably 20g / 10 minutes. The upper limit of MFR is more preferably 17g / 10 minutes, further preferably 16g / 10 minutes, and particularly preferably 15g / 10 minutes. If it is within the above range, stretching becomes easy, or the thickness unevenness becomes smaller, or it is easy to increase the stretching temperature and the heat setting temperature, and the dimensional change during heating becomes smaller, and the heat resistance is improved, so it is preferred.
[0059] From the viewpoint of heat resistance, the aforementioned substrate film may be a uniaxially stretched film in the longitudinal direction (MD direction) or the transverse direction (TD direction), preferably a biaxially stretched film. In the present invention, by using the aforementioned preferred raw materials and stretching at least along a single axis, a film having a smaller dimensional change when heated and high heat resistance, which is unexpected in conventional polypropylene films, can be obtained. As stretching methods, simultaneous biaxial stretching method, successive biaxial stretching method, etc. can be cited. From the viewpoint of making planarity, dimensional stability, uneven thickness, etc. good, the successive biaxial stretching method is preferably used.
[0060] As a sequential biaxial stretching method, a polypropylene resin is heated and melted by a single-screw or twin-screw extruder in a manner that the resin temperature is 200°C or more and 280°C or less, and a sheet is formed through a T die, and extruded on a cooling roll at a temperature of 10°C or more and 100°C or less to obtain an unstretched sheet. Next, the sheet may be roll stretched to 3.0 times or more and 8.0 times or less along the longitudinal direction (MD direction) at 120°C or more and 165°C or less, and then, after preheating by a tenter, the sheet may be stretched to 4.0 times or more and 20.0 times or less along the transverse direction (TD direction) at a temperature of 155°C or more and 175°C or less. Furthermore, after biaxial stretching, the sheet may be subjected to a heat fixation treatment while being relaxed by 1% or more and 15% or less at a temperature of 165°C or more and 175°C or less.
[0061] In the present invention, as an index of dimensional change during heating, the heating elongation of the aforementioned substrate film at 130°C measured by a thermomechanical analyzer is preferably 10% or less in both the MD direction and the TD direction. As a result, in the processing step of the gas barrier layer, the lamination processing step, and the sealing step described later, the deformation of the substrate caused by the thermal load in the state where tension is applied to the film can be reduced. As a result, the gas barrier performance, the adhesive performance, and the appearance quality such as wrinkle relaxation can be further improved. The heating elongation in the MD direction and the TD direction at 130°C is preferably 9.5% or less, more preferably 9.0% or less, and further preferably 8.5% or less, and the lower limit is preferably 0%. When the heating elongation at 130°C exceeds the above range, the laminated film is sometimes deformed due to the heat when the tension is applied, so that the gas barrier property is reduced, or the dimensional change of the film occurs, and the appearance quality is reduced. In the present invention, the heating elongation is a value measured by a thermomechanical analyzer (TMA) method, and more specifically, it is based on the method described in the embodiment.
[0062] In order to adjust the heating elongation to the above range, the base film of the present invention is preferably formed by the following method.
[0063] First, the upper limit of the stretching temperature in the longitudinal direction (MD) is preferably the film melting point (Tm) - 7° C., more preferably Tm - 10° C., and further preferably Tm - 12° C. Within the above range, the heating elongation is easily reduced, and the film is less likely to be welded to the stretching roll and less likely to be stretched, so that the quality is less likely to be reduced.
[0064] It should be noted that the stretching in the longitudinal direction can be carried out in multiple stages, using three or more pairs of stretching rollers, divided into two or more stages. By dividing into multiple stages, the deformation during stretching can be reduced, and therefore, the heating elongation can be easily reduced.
[0065] The upper limit of the stretching ratio in the width direction (TD) is preferably 15 times, more preferably 12 times, and further preferably 10 times. If it exceeds the above, the elongation during heating becomes high and the film is easily broken during stretching.
[0066] In addition, the lower limit of the TD stretching temperature is preferably 150°C, more preferably 152°C, further preferably 154°C, and particularly preferably 156°C. If it is 150°C or more, stretching is performed in a sufficiently softened state, so it is easy to reduce the heating elongation. The upper limit of the TD stretching temperature is preferably 164°C, more preferably 162°C, and further preferably 160°C. In order to reduce the heating elongation, it is preferred that the temperature is high.
[0067] The lower limit of the heat setting temperature after stretching in the width direction (TD) is preferably 168° C., more preferably 170° C., and further preferably 173° C. When it is 168° C. or higher, the heat elongation is unlikely to increase, and a long treatment time is not required to reduce the heat elongation.
[0068] It is preferred to relax the film during heat setting. The lower limit of the relaxation rate is preferably 2%, and more preferably 3%. If the lower limit is less than the above, the elongation after heating may become high.
[0069] Furthermore, in order to reduce the heat shrinkage rate, the film produced through the above steps may be once rolled into a roll and then annealed off-line.
[0070] Regarding the substrate film used in the present invention, in order to impart operability (for example, windability after lamination), it is preferred that the film contain particles to form protrusions on the film surface. As particles contained in the film, inorganic particles such as silica, kaolinite, talc, calcium carbonate, zeolite, and alumina can be listed; heat-resistant polymer particles such as acrylic, PMMA, nylon, polystyrene, polyester, and benzoguanamine-formaldehyde condensate. From the viewpoint of transparency, it is preferred that the content of particles in the film is small, for example, preferably more than 1 ppm and less than 1000 ppm. In addition, the average particle size of the particles is preferably 1.0 to 3.0 μm, and more preferably 1.0 to 2.7 μm. The method for determining the average particle size mentioned here is to take a photograph using a scanning electron microscope, use an image analyzer to measure the Feret diameter in the horizontal direction, and express it as its average value. Furthermore, from the viewpoint of transparency, it is preferred to select particles having a refractive index close to that of the resin used. Furthermore, in order to impart various functions to the film as required, an antioxidant, ultraviolet absorber, antistatic agent, pigment, lubricant, nucleating agent, adhesive, antifogging agent, flame retardant, antiblocking agent, inorganic filler or organic filler may be contained.
[0071] In addition to the polypropylene resin used in the present invention, other resins may be used within the scope that does not impair the purpose of the present invention in order to improve the mechanical properties of the base film and the adhesion to the ink layer and adhesive layer laminated on the aforementioned gas barrier coating layer, reduce environmental burden, etc. Examples thereof include polyethylene resins, polypropylene resins different from the aforementioned, random copolymers that are copolymers of propylene and ethylene and / or α-olefins having 4 or more carbon atoms, and various elastomers.
[0072] The polyethylene resin used for the substrate film in the present invention is a resin with ethylene as the main component, and any ethylene homopolymer such as high-pressure low-density polyethylene, linear low-density polyethylene, medium-density polyethylene and high-density polyethylene can be used. In addition, crystalline or low-crystalline or even non-crystalline random or block copolymers formed with α-olefins such as propylene, 1-butene, 1-pentene, 1-hexene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-octene, vinyl acetate, (meth)acrylic acid, (meth)acrylates, etc., or mixtures thereof can be used.
[0073] The polyethylene resin preferably contains 1% by mass or more and 25% by mass or less relative to the total of 100 of the polypropylene resin and the polyethylene resin constituting the substrate. If it is 1% by mass or more, the heat seal strength, anti-blocking property and anti-fogging property are improved. More preferably, it is 5% by mass or more, and more preferably, it is 8% by mass or more. If it is 20% by mass or less, it is easy to maintain rigidity. More preferably, it is 18% by mass or less, and more preferably, it is 15% by mass or less.
[0074] The melting point of the polyethylene resin is preferably 100° C. to 135° C., more preferably 105° C. to 130° C., from the viewpoints of heat resistance, transparency, mechanical properties, and film forming properties. The density is preferably 0.90 g / cm 3 Above 0.94g / cm 3 Below, more preferably 0.91 g / cm 3 Above 0.94g / cm 3 the following.
[0075] The melt flow rate (MFR) (190°C, 2.16 kgf) of the polyethylene resin is preferably 0.5 g / 10 min or more, more preferably 1 g / 10 min or more, and further preferably 2 g / 10 min or more. From the viewpoint of further stabilizing the moldability, it is preferably 20 g / 10 min or less, more preferably 15 g / 10 min or less, and further preferably 10 g / 10 min or less.
[0076] From the viewpoint of low environmental burden, the polyethylene resin of the present invention is particularly preferably a polyethylene resin derived from plants. The biobase content of the polyethylene resin measured according to ISO16620 is preferably 50% or more and 100% or less, more preferably 70% or more and 100% or less, and further preferably 80% or more and 100% or less.
[0077] In the present invention, the thickness of the substrate film is arbitrarily set according to each use, and the lower limit is preferably 2 μm or more, more preferably 3 μm or more, and further preferably 4 μm or more. On the other hand, the upper limit of the thickness is preferably 300 μm or less, more preferably 250 μm or less, further preferably 200 μm or less, and particularly preferably 150 μm or less. In the case of thin thickness, the handling property is easy to become poor. On the other hand, in the case of thick thickness, not only there are problems in terms of cost, but also in the case of winding into a roll for storage, it is easy to produce poor planarity caused by curling habit (rolling habit).
[0078] From the viewpoint of visibility of the contents, the haze of the substrate film of the present invention is preferably transparent, and specifically preferably 6% or less, more preferably 5% or less, and further preferably 4% or less. For example, when the stretching temperature or heat setting temperature is too high, when the cooling roll (CR) temperature is high, when the cooling speed of the stretched original roll is slow, and when the low molecular weight is too high, there is a tendency for the haze to deteriorate, and therefore, by adjusting these, it can be controlled within the above range.
[0079] In addition, as long as the purpose of the present invention is not impaired, the base film layer in the present invention may be subjected to corona discharge treatment, glow discharge treatment, flame treatment, surface roughening treatment, and may also be subjected to known anchor coating treatment, printing, decoration, etc. In the anchor coating, a resin with good adhesion such as polyurethane and polyester is generally suitable. The anchor coating used to improve the barrier in the present invention will be described later.
[0080] The packaging material of the present invention requires at least one substrate film having a gas barrier layer, but by laminating more than two substrate films, it is expected that the toughness and gas barrier performance of the packaging material can be improved, so it is more preferred. In terms of toughness, by using two polypropylene biaxially stretched films that generally have the characteristic of large puncture strength, it is possible to achieve a packaging material design that is not inferior to the structure of two different raw materials used for polyester films and polyamide films widely used as packaging materials. In addition, in terms of gas barrier properties, by using two substrate films, the film in the middle is not easily affected by the external environment, such as temperature and humidity, external bending, etc., and can exert a more stable gas barrier performance. In this sense, when using two substrate films, the covering layer and inorganic film layer with gas barrier performance are particularly preferably laminated on the middle film.
[0081] [Gas barrier layer]
[0082] In the present invention, at least one of the aforementioned substrate films needs to be a laminated substrate film having a gas barrier layer. It should be noted that as the gas barrier layer, it is preferred to laminate any of the following covering layers (A) having an organic substance as a main component or the following inorganic thin film layer (B) having an inorganic substance as a main component. Furthermore, in order to assist the barrier properties of the gas barrier layer, the following anchor coating layer (C) and protective layer (D) may also be laminated in combination.
[0083] [Coating layer (A)]
[0084] In the present invention, a covering layer (A) may be provided as a gas barrier layer. However, in the present invention, it is necessary to design the film with consideration of the environmental loads such as the increase in cost due to the increase in steps caused by providing the covering layer (A) and the difficulty in recycling due to the film thickness.
[0085] The coating weight of the coating layer (A) is preferably 0.10 to 0.70 (g / m 2 The lower limit of the amount of coating layer (A) is preferably 0.15 (g / m 2 ) or more, more preferably 0.20 (g / m 2 ) or more, more preferably 0.25 (g / m 2 ) or more, and the upper limit is preferably 0.65 (g / m 2 ) or less, more preferably 0.60 (g / m2 ) or less, more preferably 0.55 (g / m 2 ) or less. If the coating weight of the coating layer (A) exceeds 0.70 (g / m 2 ), the gas barrier properties are improved, but the cohesive force inside the covering layer becomes insufficient, and the uniformity of the covering layer is also reduced, so sometimes unevenness (increased haze, whitening) or defects occur in the coating appearance, or the gas barrier properties / adhesion cannot be fully demonstrated. In addition, in terms of processability, adhesion may also occur due to the thick film thickness. Furthermore, there are concerns that the recyclability of the film will be adversely affected, and the amount of raw materials / solvents used will also increase, so the environmental load becomes stronger. On the other hand, if the adhesion amount of the covering layer (A) is less than 0.10 (g / m 2 ), sufficient gas barrier properties and interlayer adhesion may not be obtained.
[0086] The resin composition used in the covering layer (A) formed on the surface of the laminated film of the present invention preferably contains a resin selected from the group consisting of polyvinyl alcohol resins, polyester resins and polyurethane resins as a constituent component, and it is desirable to contain a polyvinyl alcohol polymer (resin). The polyvinyl alcohol polymer has vinyl alcohol units as the main constituent components, and it can be expected that the barrier performance caused by the high cohesion brought about by the hydrogen bond structure will be greatly improved. The degree of polymerization and saponification of the polyvinyl alcohol polymer are determined by the target gas barrier properties and the viscosity of the coating aqueous solution. Regarding the degree of polymerization, since the aqueous solution has a high viscosity and is easy to gel, it becomes difficult to coat. From the perspective of coating operability, it is preferably less than 2600. Regarding the degree of saponification, when it is less than 90%, sufficient oxygen barrier properties under high humidity cannot be obtained. If it exceeds 99.7%, the adjustment of the aqueous solution is difficult, it is easy to gel, and it is not suitable for industrial production. Therefore, the degree of saponification is preferably 90 to 99.7%, and more preferably 93 to 99%. In the present invention, various copolymerized or modified polyvinyl alcohol polymers such as polyvinyl alcohol polymers copolymerized with ethylene and polyvinyl alcohol polymers modified with silanol may be used within the range not impairing processability and productivity.
[0087] The cover layer (A) of the present invention may contain an inorganic layered compound. By the presence of an inorganic layered compound, a labyrinth effect on gas can be expected to improve gas barrier properties. In addition, by adding an inorganic layered compound, the humidity dependence of gas barrier properties can be suppressed. As materials, clay minerals such as smectite, kaolin, mica, hydrotalcite, and chlorite (including synthetic products thereof) can be listed. Specifically, montmorillonite, beidellite, saponite, hectorite, zinc soapstone, stony soapstone, kaolinite, pearl clay, dickite, halloysite, hydrated halloysite, tetrasilicon mica, sodium band mica, muscovite, pearl mica, phlogopite, talc, antigorite, chrysotile, pyrophyllite, vermiculite, yellow green brittle mica, chlorite, etc. can be listed. Furthermore, as an inorganic layered compound, flaky silica, etc. can also be used. These can be used alone or in combination of two or more. Among them, smectite (including synthetic products thereof) is particularly preferred because of its high effect of improving water vapor barrier properties.
[0088] In addition, as an inorganic layered compound, it is preferred that a metal ion having redox properties, particularly an iron ion, is present therein. Furthermore, among such substances, montmorillonite, which is a type of montmorillonite, is preferred from the aspects of coating adaptability and gas barrier properties. As montmorillonite, a well-known substance that has been used as a gas barrier agent can be used. For example, the following general formula:
[0089] (X,Y) 2~3 Z4O 10 (OH)2·mH2O·(Wω)
[0090] (In the formula, X represents Al, Fe(III) or Cr(III). Y represents Mg, Fe(II), Mn(II), Ni, Zn or Li. Z represents Si or Al. W represents K, Na or Ca. H2O represents interlayer water. m and ω represent positive real numbers.)
[0091] Among these, W in the formula is preferably Na from the viewpoint of cleavage in an aqueous medium.
[0092] The size and shape of the inorganic layered compound are not particularly limited. As a particle size (major diameter), it is preferably 5 μm or less, more preferably 4 μm or less, and further preferably 3 μm or less. If the particle size is greater than 5 μm, the dispersibility is poor, and as a result, the coating property and coating appearance of the covering layer (A) may be deteriorated. On the other hand, as its aspect ratio, it is 50 to 5000, more preferably 100 to 4000, and further preferably 200 to 3000.
[0093] The blending ratio of the resin composition and the inorganic layered compound in the covering layer of the present invention is preferably 75 / 25 to 35 / 65 (mass %), more preferably 70 / 30 to 40 / 60 (mass %), and further preferably 65 / 35 to 45 / 55 (mass %). If the blending ratio of the inorganic layered compound is less than 25%, the barrier performance may be insufficient. On the other hand, if it is more than 65%, the dispersibility may deteriorate, the coating property may deteriorate, and the adhesion may deteriorate.
[0094] In order to improve the cohesive force of the film and improve the moisture-heat resistance and adhesion, the covering layer (A) of the present invention can be mixed with various crosslinking agents within the range that does not damage the gas barrier properties and productivity. As the crosslinking agent, for example, silicon-based crosslinking agents, oxazoline compounds, carbodiimide compounds, epoxy compounds, isocyanate compounds, etc. can be exemplified. Among them, by mixing with a silicon-based crosslinking agent, a crosslinking reaction can be carried out with a resin composition having a hydroxyl group and an inorganic thin film layer. From the viewpoint of improving water-resistant adhesion, silicon-based crosslinking agents are particularly preferred. As commonly used silicon-based crosslinking agents, metal alkoxides and silane coupling agents can be listed. Metal alkoxides are represented by the general formula M(OR) n (M: metal of Si, Al, R: alkyl such as CH3, C2H5) represented by a compound. Specifically, tetraethoxysilane〔Si(OC2H5)4〕, triisopropoxyaluminum〔Al[OCH(CH3)2]3〕, etc. can be exemplified. As silane coupling agents, substances having epoxy groups such as 3-glycidoxypropyltrimethoxysilane, substances having amino groups such as 3-aminopropyltrimethoxysilane, substances having mercapto groups such as 3-mercaptopropyltrimethoxysilane, substances having isocyanate groups such as 3-isocyanatepropyltriethoxysilane, tris(3-trimethoxysilylpropyl)isocyanurate, etc. can be exemplified. As other crosslinking agents, oxazoline compounds, carbodiimide compounds, epoxy compounds, etc. can be used in combination. Among them, when recyclability is emphasized, the amount of crosslinking agent to be mixed needs to be considered.
[0095] When the crosslinking agent is mixed, the amount thereof is preferably 0.05 to 4.00% by mass in the covering layer, more preferably 0.10 to 3.50% by mass, and further preferably 0.15 to 3.00% by mass. By setting the above range, the curing of the film proceeds, the cohesion is improved, and as a result, a film with excellent water-resistant adhesiveness can be made. If the amount of the mixture exceeds 4.00% by mass, the amount of the uncrosslinked part increases, the curing is excessively carried out, and the film hardens, thereby the adhesiveness may be reduced instead. On the other hand, if the amount of the mixture is less than 0.05% by mass, sufficient cohesion may not be obtained.
[0096] In the present invention, from the viewpoint of visibility of the contents, the haze of the film after the covering layer (A) is laminated is preferably 20% or less, more preferably 18% or less, and further preferably 16% or less. If the haze is greater than 20%, not only the transparency is greatly deteriorated, but also the surface irregularities may be affected, which may lead to poor appearance in subsequent printing processes, etc. It should be noted that the haze can be adjusted by the composition ratio of the covering layer (A), solvent conditions, film thickness, etc. Here, the haze is evaluated according to JIS K7136 using a turbidity meter (NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd.).
[0097] The coating method of the resin composition for the covering layer (A) is not particularly limited as long as it is a method of coating the film surface to form a layer. For example, a common coating method such as gravure coating, reverse roll coating, wire bar coating, die coating, etc. can be used.
[0098] When forming the covering layer (A), it is preferred to pre-dry at a relatively low temperature after applying the resin composition for the covering layer (A), first volatilize the solvent, and then perform main drying at a high temperature, so that a uniform film can be obtained. The pre-drying temperature is preferably 80 to 110°C, more preferably 85 to 105°C, and further preferably 90 to 100°C. If the pre-drying temperature is lower than 80°C, insufficient drying may occur in the covering layer. In addition, if the pre-drying temperature is higher than 110°C, drying is performed before the covering layer is wetted and spread, which may result in poor appearance.
[0099] On the other hand, the main drying temperature is preferably 110 to 140°C, more preferably 115 to 135°C, and even more preferably 120 to 130°C. If the main drying temperature is lower than 110°C, the film formation of the cover layer (A) does not proceed, the cohesive force and the adhesiveness decrease, and as a result, the barrier properties may be adversely affected. If it exceeds 140°C, the film may be overheated and become brittle, or wrinkles due to heat shrinkage may become larger.
[0100] The drying time of the pre-drying is preferably 3.0 to 10.0 seconds, more preferably 3.5 to 9.5 seconds, and further preferably 4.0 to 9.0 seconds. In addition, the drying time of the main drying is preferably 3.0 to 10.0 seconds, more preferably 3.5 to 9.5 seconds, and further preferably 4.0 to 9.0 seconds. However, the drying conditions also vary depending on the type of heat medium and the intake and exhaust conditions of the drying furnace, so attention should be paid. In addition, unlike drying, additional heating treatment for 1 to 4 days in a low temperature range, specifically in a temperature range of 40 to 60°C, is also more effective in film formation of the covering layer (A).
[0101] [Inorganic thin film layer (B)]
[0102] In the present invention, as a gas barrier layer, an inorganic thin film layer (B) may be provided on the surface of the aforementioned substrate film. The inorganic thin film layer (B) is a thin film formed of a metal or an inorganic oxide. The material forming the inorganic thin film layer is not particularly limited as long as it can be made into a thin film, and is preferably selected from the group consisting of aluminum, aluminum oxide, silicon oxide, and a composite oxide of silicon oxide and aluminum oxide. From the viewpoint of gas barrier properties, inorganic oxides such as silicon oxide (silicon dioxide), aluminum oxide (alumina), a composite oxide of silicon oxide and aluminum oxide, and a mixture can be preferably cited. In particular, from the aspect of being able to take into account the softness and density of the film layer, a composite oxide of silicon oxide and aluminum oxide is preferably used. In the composite oxide, the mixing ratio of silicon oxide to aluminum oxide is preferably in the range of 20 to 70% by mass of Al in terms of the mass ratio of the metal components. If the Al concentration is less than 20% by mass, the water vapor barrier property sometimes decreases. On the other hand, if it exceeds 70% by mass, there is a tendency for the inorganic thin film layer to harden, and during secondary processing such as printing and lamination, the film may be destroyed and the gas barrier property may be reduced. It should be noted that the silicon oxide mentioned here refers to various silicon oxides such as SiO and SiO2 or mixtures thereof, and the aluminum oxide refers to various aluminum oxides such as AlO and Al2O3 or mixtures thereof.
[0103] The film thickness of the inorganic thin film layer (B) is usually 1 to 100 nm, preferably 5 to 50 nm. If the film thickness of the inorganic thin film layer (B) is less than 1 nm, it is sometimes difficult to obtain satisfactory gas barrier properties. On the other hand, even if it is too thick exceeding 100 nm, it is impossible to obtain a comparable improvement in gas barrier properties, which is disadvantageous in terms of bending resistance and manufacturing cost.
[0104] There is no particular limitation on the method for forming the inorganic thin film layer (B), and any known evaporation method such as physical evaporation method (PVD method) such as vacuum evaporation method, sputtering method, ion plating method, or chemical evaporation method (CVD method) can be appropriately used. Below, a typical method for forming an inorganic thin film layer (B) is described by taking a silicon oxide / aluminum oxide thin film as an example. For example, in the case of using a vacuum evaporation method, a mixture of SiO2 and Al2O3, or a mixture of SiO2 and Al, etc. is preferably used as an evaporation raw material. As these evaporation raw materials, particles are usually used, but at this time, it is desired that the size of each particle is such that the pressure does not change during evaporation, and the preferred particle size is 1mm to 5mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, etc. In addition, reactive evaporation by introducing oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, etc. as a reaction gas, or by using ozone addition, ion assistance, etc. Furthermore, the film forming conditions can be arbitrarily changed by applying a bias voltage to the vapor-deposited body (the laminated thin film for vapor deposition), or by heating or cooling the vapor-deposited body. Such vapor deposition materials, reaction gases, bias voltage, heating / cooling of the vapor-deposited body, etc. can also be changed in the same manner when sputtering or CVD is used.
[0105] [Anchor coating (C)]
[0106] In the present invention, as an auxiliary layer for showing sufficient gas barrier properties and adhesion when the aforementioned gas barrier layer is stacked, an anchor coating (C) may be provided. By having an anchor coating (C), it is possible to suppress the exposure of oligomers and anti-blocking agents from the polypropylene resin, so it is preferred. Furthermore, when other layers are stacked on the anchor coating (C), the interlayer adhesion can also be improved. In particular, in the formation of the inorganic film layer (B), not only the adhesion can be expected, but also the effect of improving the gas barrier properties by promoting the formation of the inorganic film layer (B) by smoothing the surface. On this basis, by using a material having a certain degree of gas barrier properties (set as gas barrier auxiliary) in the anchor coating (C) itself, the gas barrier performance of the film when the aforementioned gas barrier layer is stacked can also be greatly improved, so it is preferred. Furthermore, the anchor coating (C) prevents hot water from intruding into the substrate, so as a result, the whitening of the film after boiling and steaming can also be reduced, so it is preferred.
[0107] In the present invention, it is preferred that the adhesion amount of the anchor coating layer (C) be 0.10 to 0.50 g / m 2 . Thus, the anchor coating layer (C) can be uniformly controlled during coating, so that the result is a film with less uneven coating and fewer defects, which is preferred. Furthermore, the anchor coating layer (C) helps to suppress the exposure of oligomers and stabilize the haze after wet heat, which is preferred. The adhesion amount of the anchor coating layer (C) is preferably 0.15 g / m 2 More preferably 0.20 g / m 2More preferably, 0.35 g / m 2 Above, preferably 0.50g / m 2 Below, more preferably 0.45g / m 2 Below, more preferably 0.40g / m 2 If the anchor coating (C) adhesion exceeds 0.50 g / m 2 , the gas barrier assistance is improved, but the cohesive force inside the anchor coating becomes insufficient, and the uniformity of the anchor coating is also reduced, so the coating appearance becomes uneven and defective. In addition, in terms of processability, due to the thick film thickness, adhesion may occur or manufacturing costs may be incurred. Furthermore, there are concerns that the recyclability of the film may be adversely affected, and the amount of raw materials / solvents used may also increase, so the environmental load becomes stronger. On the other hand, if the film thickness of the anchor coating (C) is less than 0.10 g / m 2 , it may not be possible to obtain sufficient gas barrier assistance and interlayer adhesion.
[0108] Examples of the resin composition used in the anchor coating (C) of the present invention include resin compositions obtained by adding epoxy, isocyanate, melamine or other curing agents to urethane, polyester, acrylic, titanium, isocyanate, imide, polybutadiene or other resins. Crosslinking agents such as silicon-based crosslinking agents, oxazoline compounds, carbodiimide compounds and epoxy compounds may also be included.
[0109] In particular, by making the anchor coating (C) contain a urethane resin, the polar group interacts with the inorganic thin film layer (B) on the basis of the barrier performance brought about by the high cohesion of the urethane bond itself, and the presence of the amorphous part also has flexibility, so damage can be suppressed even when a bending load is applied, which is preferred. In addition, polyester resin can also be expected to have the same effect, so it is suitable. In the present invention, it is particularly preferred to contain a polyurethane composed of polyester + isocyanate, and further, from the viewpoint of being able to improve adhesion, it is more preferred to add a silicon-based crosslinking agent.
[0110] The urethane resin used in the anchor coating (C) of the present invention is preferably a urethane resin containing an aromatic or aromatic aliphatic diisocyanate component as a main component from the viewpoint of gas barrier assistance. Among them, it is particularly preferred to contain meta-xylylene diisocyanate. By using such a resin, the cohesive force of the urethane bond can be further increased by the stacking effect of the aromatic rings, and as a result, good gas barrier assistance can be obtained.
[0111] In the present invention, the ratio of the aromatic or aromatic aliphatic diisocyanate in the urethane resin used in the anchor coating (C) is preferably set to a range of 50 mol% or more (50 to 100 mol%) in 100 mol% of the polyisocyanate component. The total amount of the aromatic or aromatic aliphatic diisocyanate is preferably 60 to 100 mol%, more preferably 70 to 100 mol%, and further preferably 80 to 100 mol%. If the total amount of the aromatic or aromatic aliphatic diisocyanate is less than 50 mol%, good gas barrier auxiliary properties may not be obtained.
[0112] In the urethane resin used in the anchor coating (C) of the present invention, various crosslinking agents can be mixed in order to improve the cohesive force of the film and improve the moisture-heat resistant adhesion. As the crosslinking agent, for example, silicon-based crosslinking agents, oxazoline compounds, carbodiimide compounds, epoxy compounds, etc. can be exemplified. Among them, silicon-based crosslinking agents are particularly preferred from the viewpoint of being able to improve the water-resistant adhesion with the inorganic thin film layer by mixing with silicon-based crosslinking agents. In addition, as the crosslinking agent, oxazoline compounds, carbodiimide compounds, epoxy compounds, etc. can also be used in combination.
[0113] As the silicon-based crosslinking agent, from the viewpoint of crosslinking of inorganic and organic substances, a silane coupling agent is preferred. As the silane coupling agent, hydrolyzable alkoxysilane compounds can be cited, for example, halogen-containing alkoxysilanes (chloro C2-4 alkyl tri C1-4 alkoxysilanes such as 2-chloroethyltrimethoxysilane, 2-chloroethyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, etc.), alkoxysilanes having epoxy groups [2-glycidyloxyethyltrimethoxysilane, 2-glycidyloxyethyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane], C2-4 alkyltriC1-4 alkoxysilanes such as glycidyloxy C2-4 alkyltriC1-4 alkoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, glycidyloxydiC2-4 alkyldiC1-4 alkoxysilanes such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-(3,4-epoxycyclohexyl)propyltrimethoxysilane, (epoxycycloalkyl)C2-4 alkyltriC1-4 alkoxysilanes having an amino group Alkoxysilanes [amino C2-4 alkyl tri C1-4 alkoxysilanes such as 2-aminoethyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, amino di C2-4 alkyl di C1-4 alkoxysilanes such as 3-aminopropyl methyl dimethoxysilane, 3-aminopropyl methyl diethoxysilane, 2-[N-(2-aminoethyl) amino] ethyl trimethoxysilane, 3-[N-(2-aminoethyl) amino] propyl trimethoxysilane, 3-[N-(2-aminoethyl) amino] propyl triethoxysilane] (amino C2-4 alkyl)aminodi C2-4 alkyldi C1-4 alkoxysilane, etc.], alkoxysilane having a mercapto group (mercapto C2-4 alkyltri C1-4 alkoxysilane such as 2-mercaptoethyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, etc.;
[0063] The invention also includes but is not limited to mercaptodi C2-4 alkyldi C1-4 alkoxysilanes such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropylmethyldiethoxysilane, etc.), alkoxysilanes having a vinyl group (vinyltrimethoxysilane, vinyltriethoxysilane and other vinyltriC1-4 alkoxysilanes, etc.), alkoxysilanes having an ethylenically unsaturated bond group [2-(meth)acryloxyethyltrimethoxysilane, 2-(meth)acryloxyethyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane and other (meth)acryloxyC2-4 alkyltriC1-4 alkoxysilanes, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane and other (meth)acryloxydi C2-4 alkyldiC1-4 alkoxysilanes, etc.] and the like. These silane coupling agents can be used alone or in combination of two or more. Among these silane coupling agents, silane coupling agents having amino groups are preferred. ;
[0114] It is preferred to add 0.05 to 4.00% by mass of a silicon-based crosslinking agent to the anchor coating (C), more preferably 0.10 to 3.50% by mass, and even more preferably 0.15 to 3.00% by mass. By adding a silicon-based crosslinking agent, the curing of the film proceeds, the cohesion is improved, and the result is a film with excellent water-resistant adhesion. Furthermore, the effect of preventing oligomer exposure can also be expected, so it is preferred. If the added amount exceeds 4.00% by mass, the curing of the film proceeds, the cohesion is improved, but a part of the unreacted part is also generated, and the adhesion between the layers may be reduced. On the other hand, if the added amount is less than 0.05% by mass, sufficient cohesion may not be obtained.
[0115] The polyester resin used in the anchor coating (C) of the present invention is produced by polycondensation of a polycarboxylic acid component and a polyol component. The molecular weight of the polyester resin is not particularly limited as long as it can provide sufficient film toughness, coating adaptability, and solvent solubility as a coating agent, and is 1000 to 50000 in number average molecular weight, and is more preferably 1500 to 30000. The functional group at the end of the polyester is also not particularly limited, and may be an alcohol end, a carboxylic acid end, or both. However, when an isocyanate curing agent is used in combination, it is necessary to use a polyester polyol with an alcohol end as the main component.
[0116] The Tg of the polyester resin used in the anchor coating (C) of the present invention is preferably 10°C or higher. This is because if the temperature is lower than this, the resin becomes sticky after the coating operation, and blocking is likely to occur, making the winding operation after coating difficult. This is because if the Tg is below 10°C, even if an anti-blocking agent is added, it is difficult to prevent blocking under conditions where the pressure near the winding core is high. The more preferred temperature of Tg is 15°C or higher, and more preferably 20°C or higher.
[0117] The polyester resin used in the anchor coating (C) of the present invention is used by polycondensing a polycarboxylic acid component and a polyol component. The polycarboxylic acid component of the polyester resin used in the present invention is characterized in that it contains at least one of ortho-oriented aromatic dicarboxylic acids or their anhydrides. By setting it to ortho-orientation, the solubility in the solvent is improved, and the substrate can be evenly coated. The deviation of the barrier properties of the uniformly coated film becomes smaller, which helps to suppress the whitening caused by oligomers. In addition, by setting it to ortho-orientation, it becomes a film with excellent flexibility and the interfacial adhesion is improved, so that the damage to the substrate caused by wet heat treatment can be reduced and oligomers can be suppressed.
[0118] As aromatic polycarboxylic acids or their anhydrides substituted with carboxylic acid at the ortho position, phthalic acid or its anhydride, 2,3-naphthalene dicarboxylic acid or its anhydride, 1,2-naphthalene dicarboxylic acid or its anhydride, anthraquinone-2,3-dicarboxylic acid or its anhydride, and 2,3-anthracene dicarboxylic acid or its anhydride can be listed. These compounds can have a substituent on any carbon atom of the aromatic ring. As the substituent, chloro, bromo, methyl, ethyl, isopropyl, hydroxyl, methoxy, ethoxy, phenoxy, methylthio, phenylthio, cyano, nitro, amino, phthalimide, carboxyl, carbamoyl, N-ethylcarbamoyl, phenyl or naphthyl can be listed. In addition, if it is a polyester polyol with a content of 70 to 100 mol% relative to 100 mol% of the total components of these polycarboxylic acids, the barrier property is improved. The effect is high, and the solvent solubility required as a coating agent is excellent, so it is particularly preferred.
[0119] In the present invention, other polycarboxylic acid components may be copolymerized within the scope of not impairing the effects of the invention. Specifically, as aliphatic polycarboxylic acids, succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, etc. may be used alone or in the form of a mixture of two or more thereof; as polycarboxylic acids containing unsaturated bonds, maleic anhydride, maleic acid, fumaric acid, etc. may be used alone or in the form of a mixture of two or more thereof; as alicyclic polycarboxylic acids, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, etc. may be used alone or in the form of a mixture of two or more thereof; as aromatic polycarboxylic acids, Polybasic acids such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, diphenyl carboxylic acid and its anhydride, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid and anhydride or ester-forming derivatives of these dicarboxylic acids, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid and ester-forming derivatives of these dihydroxycarboxylic acids are used alone or in a mixture of two or more thereof. Among them, succinic acid, 1,3-cyclopentane dicarboxylic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, and diphenyl carboxylic acid are preferred from the viewpoint of organic solvent solubility and gas barrier properties.
[0120] The polyol component of the polyester used in the anchor coating (C) of the present invention is not particularly limited as long as a polyester showing a gas barrier filling performance can be synthesized, and preferably contains at least one polyol component selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, cyclohexanedimethanol and 1,3-bishydroxyethylbenzene. Among them, it is estimated that the smaller the number of carbon atoms between oxygen atoms, the less flexible the molecular chain becomes and the less likely it is for oxygen to permeate, so it is most preferable to use ethylene glycol as the main component.
[0121] In the present invention, the polyol component is preferably used. In addition, other polyol components may be copolymerized within the range that does not impair the effect of the present invention. Specifically, as diols, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methyl pentanediol, dimethyl butanediol, butyl ethyl propanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol can be listed, and as trivalent or higher alcohols, glycerol, trimethylolpropane, trimethylolethane, tris(2-hydroxyethyl)isocyanurate, 1,2,4-butanetriol, pentaerythritol, dipentaerythritol, etc. can be listed. In particular, among the trivalent alcohols, polyesters using glycerol and tris(2-hydroxyethyl)isocyanurate in combination are particularly preferably used because they are derived from a branched structure and have a moderately high crosslinking density, so they have good organic solvent solubility and excellent barrier function.
[0122] As the catalyst used in the reaction to obtain the polyester of the present invention, tin catalysts such as monobutyl tin oxide and dibutyl tin oxide, titanium catalysts such as tetraisopropyl titanate and tetrabutyl titanate, zirconium oxide catalysts such as tetrabutyl zirconate and the like, and acid catalysts such as the like can be cited. It is preferred to use the above-mentioned titanium catalysts such as tetraisopropyl titanate and tetrabutyl titanate, which have high activity in ester reaction, in combination with the above-mentioned zirconium oxide catalyst. The amount of the catalyst is used in an amount of 1 to 1000 ppm relative to the total mass of the reaction raw materials used, and more preferably 10 to 100 ppm. If it is less than 1 ppm, it is difficult to obtain the effect as a catalyst, and if it exceeds 1000 ppm, when an isocyanate curing agent is used, it sometimes occurs that the urethane reaction is hindered.
[0123] In the present invention, when a polyester resin is used as the main agent of the coating agent constituting the anchor coating (C), it is particularly preferred to use an isocyanate curing agent as a curing agent to form a polyurethane resin. In this case, the coating becomes a cross-linked system, so it has the advantages of improved heat resistance, wear resistance, and rigidity. Therefore, it is also easy to use for boiling and retorting packaging. On the other hand, there is also a problem that the liquid cannot be reused after mixing the curing agent, and a curing (aging) process must be performed after coating. As an advantage, the following aspects can be exemplified: as a simple outer coating varnish, for example, there is no need to worry about the thickening of the coating liquid, and the management of coating manufacturing is easy, and the coating liquid can be diluted and reused, and on this basis, a curing process (so-called aging process) is not required. At this time, the terminal of the polyester used can be used without any problem, whether it is a polyol, a polycarboxylic acid, or a mixture of the two. On the other hand, since the resin of the anchor coating (C) is a straight chain, the heat resistance and abrasion resistance are sometimes insufficient, and sometimes it is difficult to use for boiling and retorting packaging.
[0124] When a curing agent is used in the anchor coating (C), since the film is coated, an isocyanate curing system is preferred from the viewpoint of the heat resistance of the film, and the resin component of the coating agent needs to be a polyester polyol. On the other hand, when an epoxy compound is used as a curing agent, a polyester polycarboxylic acid is required. In these cases, the coating becomes a cross-linked system, so it has the advantages of improved heat resistance, abrasion resistance, and rigidity. Therefore, it is also easy to use for boiling and retorting packaging. On the other hand, there is also a problem that the liquid cannot be recycled after mixing the curing agent, and a curing (aging) process must be performed after coating.
[0125] The polyisocyanate compound used in the present invention, when the polyester has a hydroxyl group, at least a portion of the reaction forms a carbamate structure, thereby becoming highly polarized as a resin component, causing polymer chains to condense, thereby further strengthening the gas barrier function. In addition, when the resin of the coating agent is a straight-chain resin, heat resistance and wear resistance can be imparted by cross-linking with a polyisocyanate having a valence of 3 or more. The polyisocyanate compound used in the present invention may be any of a diisocyanate, a polyisocyanate having a valence of 3 or more, a low molecular compound, and a high molecular compound, but from the viewpoint of improving the gas barrier function, it is preferred that a portion of the skeleton contains an aromatic ring or an aliphatic ring. For example, examples of isocyanates having an aromatic ring include toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and naphthalene diisocyanate. Examples of isocyanates having an aliphatic ring include hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, isophorone diisocyanate, and norbornane diisocyanate, or trimers of these isocyanate compounds, and terminal isocyanate group-containing compounds obtained by reacting excess amounts of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, trimethylolpropane, glycerin, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, and triethanolamine, or high molecular weight active hydrogen compounds such as various polyester polyols, polyether polyols, and polyamides.
[0126] The method for forming the anchor coating layer (C) is not particularly limited, and a conventionally known method such as a coating method can be used. Suitable coating methods include an offline coating method and an online coating method. For example, in the case of an online coating method performed in the process of manufacturing a substrate film layer, the drying and heat treatment conditions during coating also depend on the coating thickness and the conditions of the device. It is preferred that the coating be immediately fed into a stretching process in a right angle direction and dried in a preheating area or a stretching area of the stretching process. In such a case, it is generally preferred to set the temperature to about 50 to 250°C.
[0127] The coating method of the resin composition for the anchor coating layer (C) is not particularly limited as long as it is a method of coating on the film surface to form a layer. For example, a common coating method such as gravure coating, reverse roll coating, wire bar coating, die coating, etc. can be used.
[0128] When forming the anchor coating layer (C), it is preferred to heat and dry after applying the resin composition for the anchor coating layer (C), and the drying temperature at this time is preferably 100 to 145°C, more preferably 110 to 140°C, and further preferably 110 to 130°C. If the drying temperature is lower than 100°C, the anchor coating layer may be insufficiently dried. On the other hand, if the drying temperature exceeds 145°C, the film may be overheated and become brittle, or shrink and deteriorate in processability. In particular, if the solvent is first volatilized at a relatively low temperature of 80°C to 110°C immediately after coating, and then dried at above 120°C, a uniform film can be obtained, which is particularly preferred. In addition, in addition to drying, applying additional heat treatment in a low temperature range as much as possible is also more effective in forming the anchor coating film.
[0129] [Protective layer on gas barrier layer (D)]
[0130] In the present invention, a protective layer (D) may be provided on the gas barrier layer. In particular, when the gas barrier layer is an inorganic thin film layer (B), the inorganic thin film layer (B) formed by the metal oxide layer is not a completely dense film, but is dispersed with tiny defective parts. By coating the metal oxide layer with a specific protective layer (D) resin composition described later, a protective layer (D) is formed, so that the resin in the protective layer (D) resin composition penetrates into the defective part of the metal oxide layer, and as a result, the barrier property of the gas barrier layer can be stabilized. In addition, by making the protective layer (D) itself also use a material with gas barrier properties, the gas barrier performance of the laminated film will also be improved.
[0131] In the present invention, it is preferred that the amount of the protective layer (D) applied be 0.10 to 0.40 (g / m 2 ). Thus, the protective layer (D) can be uniformly controlled during coating, so that a film with uneven coating and few defects is formed, which is preferred. In addition, the cohesive force of the protective layer (D) itself is improved, and the adhesion between the gas barrier layer (especially the inorganic thin film layer (B)) and the protective layer (D) is also strengthened, which is preferred. The adhesion amount of the protective layer is preferably 0.13 (g / m 2 ) or more, more preferably 0.16 (g / m 2 ) or more, more preferably 0.19 (g / m 2 ) or more, preferably 0.37 (g / m 2 ) or less, more preferably 0.34 (g / m 2 ) or less, more preferably 0.31 (g / m 2 ) or less. If the adhesion amount of the protective layer (D) exceeds 0.40 (g / m 2), the gas barrier properties are improved, but the cohesive force inside the protective layer becomes insufficient and the uniformity of the protective layer is also reduced. Therefore, the coating appearance may be uneven or defective, or the gas barrier properties / adhesion properties may not be fully exhibited. On the other hand, if the adhesion amount of the protective layer (D) is less than 0.10 (g / m 2 ), there is a possibility that sufficient gas barrier properties and interlayer adhesion may not be obtained.
[0132] As the resin composition used in the protective layer (D) formed on the surface of the gas barrier layer (especially the inorganic thin film layer (B)) of the present invention, resins such as polyvinyl alcohol, urethane, polyester, acrylic, titanium, isocyanate, imide, and polybutadiene can be used, and further, curing agents such as epoxy, isocyanate, melamine, and silanol can be added.
[0133] The coating method of the resin composition for protective layer (D) is not particularly limited as long as it is a method of coating on the film surface to form a layer. For example, a common coating method such as gravure coating, reverse roll coating, wire bar coating, die coating, etc. can be used.
[0134] When forming the protective layer (D), it is preferred to heat and dry after applying the resin composition for the protective layer (D). The drying temperature at this time is preferably 100-160°C, more preferably 110-150°C, and further preferably 120-140°C. If the drying temperature is lower than 100°C, the protective layer (D) is insufficiently dried, or the film formation of the protective layer (D) is not carried out and the cohesion and water-resistant adhesion are reduced, resulting in reduced barrier properties and hand-tear properties. On the other hand, if the drying temperature exceeds 160°C, the film may be overheated and become brittle, the puncture strength may be reduced, or shrinkage may occur, and the processability may deteriorate. In addition, in addition to drying, applying additional heating treatment in a low temperature range as much as possible will also promote the film formation of the protective layer, which is more effective in this regard.
[0135] [Other films]
[0136] In the present invention, within the range of satisfying the single material ratio described later for packaging materials, other films other than the base film composed of polyolefin resins may be provided. Other films used in the present invention are, for example, films obtained by melt-extruding plastics and stretching, cooling, and heat-fixing in the length direction and / or width direction as required. As plastics, in addition to polyamides represented by nylon 4 / 6, nylon 6, nylon 6 / 6, nylon 12, etc., and polyesters represented by polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalate, etc., polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene vinyl alcohol, wholly aromatic polyamides, polyamide-imides, polyimides, polyetherimides, polysulfones, polystyrene, polylactic acid, etc. may also be listed.
[0137] The other films in the present invention can be any film thickness depending on the desired purpose such as mechanical strength and transparency. Although not particularly limited, 5 to 250 μm is generally recommended, and 10 to 60 μm is ideal when used as packaging materials. However, the ratio of a single material in the packaging material described later needs to be considered.
[0138] In addition, the other film in the present invention can be a laminated film of one or more plastic films. The type, number of layers, lamination method, etc. of the laminate when making the laminated film are not particularly limited and can be arbitrarily selected from known methods according to the purpose.
[0139] [Heat sealable resin film]
[0140] The heat-sealable resin film used in the present invention preferably contains a propylene-α-olefin random copolymer as a polyolefin resin composition and further contains at least one component selected from ethylene-propylene copolymer elastomer, ethylene-butene copolymer elastomer and propylene-butene copolymer elastomer.
[0141] (Propylene-α-olefin random copolymer)
[0142] In the present invention, the propylene-α-olefin random copolymer can be a copolymer of propylene and at least one of α-olefins having 2 or 4 to 20 carbon atoms other than propylene. As the α-olefin monomer having 2 or 4 to 20 carbon atoms, ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, etc. can be used. Although not particularly limited, ethylene is preferably used from the aspect of stretchability and low shrinkage. In addition, as long as at least one or more species are used, two or more species can be mixed and used as needed. Particularly suitable is a propylene-ethylene random copolymer.
[0143] The lower limit of the melt flow rate (MFR) of the propylene-α-olefin random copolymer is preferably 0.6 g / 10 min, more preferably 1.0 g / 10 min, and further preferably 1.2 g / 10 min. The upper limit of the melt flow rate of the random copolymer is preferably 12.0 g / 10 min, more preferably 9.0 g / 10 min, and further preferably 8.0 g / 10 min. If the melt flow rate is outside this range, the uniformity of the film thickness may be impaired. Specific examples of copolymers satisfying this range include propylene-ethylene random copolymers (Sumitomo Chemical Co., Ltd., SUMITOMONOBLEN WF577PG, MFR at 230°C and 2.16 kg load of 3.2 g / 10 min, melting point of 142°C), propylene-ethylene-butene random copolymers (Sumitomo Chemical Co., Ltd., SUMITOMONOBLEN FL8115A, MFR at 230°C and 2.16 kg load of 7.0 g / 10 min, melting point of 148°C), and propylene-ethylene-butene random copolymers (Sumitomo Chemical Co., Ltd., SUMITOMONOBLEN FL6745A, MFR at 230°C and 2.16 kg load of 6.0 g / 10 min, melting point of 130°C). Particularly suitable are propylene-ethylene random copolymers in which propylene is the main monomer and a predetermined amount of ethylene is copolymerized. In the present invention, the random copolymers are named and described in the order of the composition ratio of the monomers constituting the random copolymer.
[0144] The lower limit of the melting point of the propylene-α-olefin random copolymer is not particularly limited, but is preferably 120° C., more preferably 125° C. If it is lower than the above lower limit, the heat resistance may be impaired, and the inner surfaces of the bag may be welded to each other during the wet heat treatment. The upper limit of the melting point of the propylene-α-olefin random copolymer is not particularly limited, but is preferably 155° C., more preferably 150° C. If it exceeds the above upper limit, the temperature required for heat sealing may become high.
[0145] (Copolymer elastomer)
[0146] The polyolefin resin composition in the heat-sealable resin film used in the present invention may be added with a thermoplastic copolymer elastomer mainly composed of polyolefin for the purpose of improving the resistance of the packaging bag to bag breakage. The copolymer elastomer in the present invention may be used in combination with at least two or more copolymer elastomers of an olefin thermoplastic copolymer elastomer showing rubber-like elasticity near room temperature and an olefin thermoplastic copolymer elastomer showing a high Shore hardness and good transparency among elastomers. By using these in combination, even if tearing ease, poor separation and bag making properties are given, transparency, sealing and bag breakage resistance are easily obtained, so it is preferred.
[0147] As an olefin-based thermoplastic copolymer elastomer showing rubber-like elasticity at around room temperature, there is an ethylene-butene copolymer elastomer, which is an amorphous elastomer or a low-crystalline elastomer obtained by copolymerizing ethylene and butene. As an olefin-based thermoplastic copolymer elastomer showing relatively high Shore hardness and good transparency among elastomers, there is a propylene-butene copolymer elastomer, which is a crystalline elastomer obtained by copolymerizing propylene and butene.
[0148] The ideal form is to use ethylene-butene copolymer elastomer and propylene-butene copolymer elastomer with a melt flow rate (MFR) of 0.2 to 5.0 g / 10 min at 230°C and a load of 2.16 kg (or a melt flow rate (MFR) of 0.2 to 5.0 g / 10 min at 190°C and a load of 2.16 kg) and a density of 820 to 930 kg / m 3 , a material having a molecular weight distribution (Mw / Mn) of 1.3 to 6.0 as determined by GPC. If the melt flow rate (MFR) under a load of 2.16 kg is less than 0.2 g / 10 min, uniform kneading becomes insufficient and fish eyes are easily generated. In addition, if it exceeds 5.0 g / min, it is not preferred from the viewpoint of bag break resistance.
[0149] From the viewpoint of maintaining heat seal strength, impact strength and bag drop strength, the intrinsic viscosity [η] of the ethylene-butene copolymer elastomer and the propylene-butene copolymer elastomer in the present invention is preferably 1.0 to 5.0, and more preferably 1.2 to 3.0. If the intrinsic viscosity [η] is less than 1.0, uniform kneading becomes insufficient and fish eyes are easily generated. If it exceeds 5.0, it is not preferred from the viewpoint of bag break resistance and heat seal strength.
[0150] Specifically, the density can be 885 kg / m 3 , an ethylene-butene copolymer elastomer having an MFR (230°C, 2.16 kg) of 1.4 g / 10 min (Tafmer A1085S, manufactured by Mitsui Chemicals, Inc.), an ethylene-butene copolymer elastomer having an MFR (190°C, 2.16 kg) of 3.6 g / 10 min (Tafmer A-4070S, manufactured by Mitsui Chemicals, Inc.), and a density of 900 kg / m 3 , a propylene-butene copolymer elastomer having an MFR (190° C., 2.16 kg) of 3 g / 10 min (Tafmer XM7070, manufactured by Mitsui Chemicals, Inc.).
[0151] The polyolefin resin composition in the heat-seal resin film of the present invention preferably contains 2 to 9 parts by mass of ethylene-butene copolymer elastomer and 2 to 9 parts by mass of propylene-butene copolymer elastomer based on 100 parts by mass of the propylene-α-olefin random copolymer.
[0152] By containing 2 parts by mass or more of ethylene-butene copolymer elastomer and 2 parts by mass or more of propylene-butene copolymer elastomer relative to 100 parts by mass of the propylene-α-olefin random copolymer, it is easy to obtain sealing properties, bag making properties, and bag breakage resistance when the ease of tearing is imparted. By containing 9 parts by mass or less of ethylene-butene copolymer elastomer and 9 parts by mass or less of propylene-butene copolymer elastomer, it is preferred that transparency, blocking resistance, and bag breakage resistance are easily improved.
[0153] In addition, in the polyolefin resin composition, it is more preferred to contain 4 to 9 parts by mass of ethylene-butene copolymer elastomer and 4 to 9 parts by mass of propylene-butene copolymer elastomer relative to 100 parts by mass of propylene-α-olefin random copolymer. Furthermore, in the polyolefin resin composition, it is further preferred to contain 5 to 9 parts by mass of ethylene-butene copolymer elastomer and 5 to 9 parts by mass of propylene-butene copolymer elastomer relative to 100 parts by mass of propylene-α-olefin random copolymer. Furthermore, in the polyolefin resin composition, it is further preferred to contain 6 to 9 parts by mass of ethylene-butene copolymer elastomer and 6 to 9 parts by mass of propylene-butene copolymer elastomer relative to 100 parts by mass of propylene-α-olefin random copolymer.
[0154] (additive)
[0155] The polyolefin resin composition in the heat-sealable resin film of the present invention may contain an anti-blocking agent. The anti-blocking agent may be one kind, and when two or more inorganic particles with different particle sizes and shapes are mixed, complex protrusions are formed in the unevenness of the film surface, which can obtain a higher anti-blocking effect.
[0156] The anti-blocking agent to be added is not particularly limited, and inorganic particles such as spherical silica, irregular-shaped silica, zeolite, talc, mica, alumina, hydrotalcite, and aluminum borate; and organic particles such as polymethyl methacrylate and ultra-high molecular weight polyethylene may be added.
[0157] When the heat-sealable resin film is a multilayer structure of 2 or 3 layers or more, the above-mentioned additives can be added to all layers. If the surface of the layer on one side of the laminated biaxially oriented film has unevenness, it sometimes causes poor appearance of the lamination process. Therefore, it is preferably added only to the layer on the side where the films are heat-sealed to each other.
[0158] The layer on which the biaxially oriented films are laminated is called a lamination layer, and its surface is called a lamination surface. The layer on which the films are heat-sealed is called a heat-sealing layer, and its surface is called a heat-sealing surface.
[0159] The amount of the anti-blocking agent added is preferably 3000 ppm or less, and more preferably 2500 ppm or less, based on the polyolefin resin composition of the layer to which it is added. By setting the amount to 3000 ppm or less, the anti-blocking agent can be reduced from falling off.
[0160] The polyolefin resin composition in the heat-sealable resin film of the present invention may be added with an organic lubricant. The smoothness and anti-blocking effect of the laminated film are improved, and the handling property of the film becomes good. The reason for this is believed to be that the organic lubricant oozes out and exists on the film surface, thereby showing a lubricant effect and a demoulding effect.
[0161] It is preferred that an organic lubricant have a melting point above room temperature. Examples of organic lubricants include fatty acid amides and fatty acid esters. Specifically, they include oleamide, erucamide, behenamide, ethylenebisoleamide, hexamethylenebisoleamide, and ethylenebisoleamide. They can be used alone, or in combination of two or more, they are preferred because they can maintain smoothness and anti-blocking effects even in harsh environments.
[0162] In the polyolefin resin composition in the heat-sealable resin film of the present invention, an appropriate amount of antioxidant, antistatic agent, antifogging agent, neutralizer, nucleating agent, colorant, other additives and inorganic filler etc. can be mixed into any layer as needed within the scope of not damaging the purpose of the present invention. As antioxidants, phenolic and phosphite esters can be used in combination, or substances having a phenolic skeleton and a phosphite skeleton in one molecule can be used alone. As neutralizers, calcium stearate etc. can be listed.
[0163] (Method for producing heat-sealable resin film)
[0164] The heat-sealable resin film of the present invention may be a single-layer film or a multilayer film of two or more layers. In the case of a three-layer structure, the cost can be reduced without impairing the heat-sealing energy and the bag-breaking resistance by adding pellets obtained by recycling the semi-finished products manufactured in the manufacturing process and the finished film after manufacturing to the intermediate layer, or by adding a propylene-α-olefin random copolymer with a low melting point only to the sealing layer and using a propylene-α-olefin random copolymer with a high melting point as the main body in the intermediate layer and the laminating layer, etc., and using resins with slightly different compositions in each layer, the effect can be further improved.
[0165] The forming method of the heat-sealable resin film of the present invention can use, for example, an inflation method or a T-die method, but in order to improve transparency or from the ease of applying traction, the T-die method is preferably used. The cooling medium in the inflation method is air, while in contrast, a cooling roller is used in the T-die method, so it is a manufacturing method that is advantageous for increasing the cooling rate. By accelerating the cooling rate, the crystallization of the unstretched sheet can be suppressed, so it becomes advantageous to use a roller for stretching in the later process. For this reason, it is preferred to use the T-die method to manufacture the non-oriented sheet.
[0166] The lower limit of the temperature of the cooling roll when the molten raw material resin is cast to obtain the non-oriented sheet is preferably 15° C., and more preferably 20° C. If the temperature is lower than the lower limit, condensation may occur on the cooling roll, resulting in insufficient adhesion. The upper limit of the cooling roll is preferably 60° C., and more preferably 50° C. If the temperature exceeds the upper limit, the transparency may deteriorate.
[0167] The stretching method of the non-oriented sheet is not particularly limited, and for example, an inflation method, a tenter transverse stretching method, and a roll longitudinal stretching method can be used. From the perspective of ease of orientation control, a roll longitudinal stretching method is preferred. The longitudinal stretching mentioned here refers to the flow direction of the film from the step of casting the raw resin composition to the step of winding the stretched film, and the transverse direction refers to the direction perpendicular to the flow direction.
[0168] By stretching the non-oriented sheet, it is preferred to show straight-line cutting properties. This is because the structure of the molecular chain is regularly arranged along the stretching direction. The lower limit of the stretch ratio is preferably 3.3 times. If it is less than the lower limit, the yield strength is sometimes reduced, the tear strength becomes larger, or the straight-line cutting property is poor. It is more preferably 3.5 times, and more preferably 3.8 times. The upper limit of the stretch ratio is preferably 5.5 times. If it is greater than the upper limit, it is sometimes excessively oriented, the sealing energy is reduced, and the resistance to breaking of the bag after falling is deteriorated. It is more preferably 5.0 times, and more preferably 4.7 times.
[0169] The lower limit of the temperature of the stretching roller is not particularly limited, but is preferably 80°C. If it is lower than this lower limit, the tensile stress applied to the film may increase, and the thickness of the film may vary. It is more preferably 90°C. The upper limit of the temperature of the stretching roller is not particularly limited, but is preferably 140°C. If it exceeds this upper limit, not only the tensile stress applied to the film may decrease, the tear strength of the film may decrease, but also the film may be fused to the stretching roller, and it may be difficult to manufacture. It is more preferably 130°C, further preferably 125°C, and particularly preferably 115°C.
[0170] It is preferred that the temperature of the sheet is raised in advance by bringing the unstretched sheet into contact with a preheating roller before the sheet is introduced into the stretching process. The lower limit of the preheating roller temperature when stretching the non-oriented sheet is not particularly limited, and is preferably 80°C, and more preferably 90°C. If it is lower than the above lower limit, the tensile stress sometimes increases and the thickness changes. The upper limit of the preheating roller temperature is not particularly limited, and is preferably 140°C, more preferably 130°C, and further preferably 125°C. If it is above the above upper limit, the heat shrinkage and cooking shrinkage sometimes increase. This is because: it is possible to suppress thermal crystallization before stretching and reduce the residual stress after stretching.
[0171] In order to suppress thermal shrinkage, it is preferred to perform annealing on the film that has undergone the longitudinal stretching process. Annealing methods include roller heating method, tentering machine method, etc. From the perspective of equipment simplicity and ease of maintenance, roller heating method is preferred. By performing annealing, the internal stress of the film can be reduced, thereby suppressing the thermal shrinkage of the film, but sometimes it has an adverse effect on properties other than the thermal shrinkage rate. However, by using an ethylene-butene copolymer elastomer and a propylene-butene copolymer elastomer in combination, its adverse effects can be suppressed.
[0172] The lower limit of the annealing temperature is not particularly limited, but is preferably 80°C. If the temperature is lower than the above lower limit, the heat shrinkage may increase, the tear strength may increase, or the finishing of the packaging bag after bag making or retorting may deteriorate. It is more preferably 100°C, and particularly preferably 110°C. The upper limit of the annealing temperature is preferably 140°C. When the annealing temperature is high, the heat shrinkage is easily reduced. If the temperature is below 140°C, uneven film thickness is unlikely to occur, the film is not easily welded to the manufacturing equipment, or the transparency, sealing, and bag breakage resistance are not easily reduced. It is more preferably 135°C, and particularly preferably 130°C.
[0173] In the annealing process, a relaxation process can be provided by reducing the rotation speed of the rollers, and then slowing down the conveying speed of the film. By providing a relaxation process, the thermal shrinkage of the heat-sealable resin film to be manufactured can be reduced. The upper limit of the relaxation rate in the relaxation process is preferably 10%, and more preferably 8%. If it is less than 10%, the film in the conveying is not easy to relax, and it is not easy to get entangled in the process, so it is preferred. The lower limit of the relaxation rate is preferably 1%, and more preferably 3%. If it is more than 1%, the thermal shrinkage of the heat-sealable resin film is not easy to increase, so it is preferred.
[0174] In the present invention, the surface of the heat-sealable resin film on which the biaxially oriented film as another material is laminated is preferably activated by corona treatment, etc. This treatment improves the lamination strength with the base film.
[0175] (Thickness of film)
[0176] The lower limit of the thickness of the heat-sealable resin film of the present invention is preferably 20 μm, more preferably 30 μm, further preferably 40 μm, and particularly preferably 50 μm. If it is 20 μm or more, it is relatively thicker than the thickness of the substrate film, so the straight-line cutting property of the laminate is not easily deteriorated, and the stiffness of the film can be obtained, and it is easy to process. In addition, it is easy to obtain impact resistance and bag breakage resistance, so it is preferred. The upper limit of the film thickness is preferably 150 μm, more preferably 100 μm, and further preferably 80 μm. If it is 150 μm or less, the stiffness of the film will not be too strong, it is easy to process, and in addition, it is easy to manufacture a suitable packaging body, so it is preferred.
[0177] (Heat shrinkage)
[0178] The upper limit of the heat shrinkage rate at 120°C in the direction with large heat shrinkage rate in the length direction and width direction of the heat-sealable resin film used in the present invention is preferably 35%, more preferably 25%. If it is less than 35%, the shrinkage during heat sealing and wet heat treatment of the package body becomes smaller, and it is not easy to damage the appearance of the package body, so it is preferred. It is more preferably 20%, and further preferably 17%. The lower limit of the heat shrinkage rate in the direction with large heat shrinkage rate in the length direction and width direction of the heat-sealable resin film of the present invention is preferably 2%. If it is more than 2%, there is no need to significantly increase the annealing temperature and annealing time, so the appearance is not easy to deteriorate, so it is preferred. The upper limit of the heat shrinkage rate in the direction with small heat shrinkage rate in the length direction and width direction of the heat-sealable resin film used in the present invention is preferably 1%. If it exceeds 1%, the tear strength in the direction with large heat shrinkage rate becomes larger or the straight-line cutting property is poor. It is preferably 0.5%. The lower limit of the heat shrinkage rate in the direction with small heat shrinkage rate in the length direction and width direction of the heat-sealable resin film used in the present invention is -5%. If it is -5% or more, the film is less likely to elongate during the heat-sealing step, and the appearance of the package is less likely to deteriorate, so it is preferred. It is more preferably -3%.
[0179] (Orientation coefficient in the length direction)
[0180] The orientation coefficient ΔNx in the longitudinal direction used in the present invention can be calculated by Formula 1.
[0181] ΔNx=Nx-(Ny+Nz) / 2 (Formula 1)
[0182] Nx: refractive index in the longitudinal direction, Ny: refractive index in the direction perpendicular to the longitudinal direction, Nz: refractive index in the plane direction
[0183] The lower limit of the orientation coefficient ΔNx in the longitudinal direction of the heat-sealable resin film of the present invention is preferably 0.010, more preferably 0.015, and further preferably 0.020. If it is 0.010 or more, it is easy to obtain the straight-line cutting property of the package body, so it is preferred. The upper limit of the orientation coefficient ΔNx in the longitudinal direction is preferably 0.0270, more preferably 0.026. If it is 0.0270 or less, the sealing strength is not easy to decrease, so it is preferred.
[0184] (Plane Orientation Coefficient)
[0185] The plane orientation coefficient ΔP used in the present invention can be calculated from the refractive index. The orientation coefficient in the plane direction can be calculated by Formula 2.
[0186] ΔP=(Nx+Ny) / 2-Nz (Formula 2)
[0187] Nx: refractive index in the longitudinal direction, Ny: refractive index in the direction perpendicular to the longitudinal direction, Nz: refractive index in the plane direction
[0188] The lower limit of the orientation coefficient ΔP in the plane direction of the heat-sealable resin film of the present invention is preferably 0.0050, and more preferably 0.0100. If it is 0.0050 or more, it is easy to obtain the puncture strength of the package, so it is preferred. In addition, by orienting the film, the rigidity required to ensure the stiff feeling can be obtained, so it is preferred. The evaluation of the ring stiffness as an indicator of the stiff feeling is described later. The upper limit of the plane orientation coefficient ΔP is preferably 0.0145, more preferably 0.0140, and further preferably 0.0130. If it is less than 0.0145, the sealing strength is not easy to decrease, so it is preferred.
[0189] [Adhesive layer]
[0190] In the packaging material of the present invention, when the substrate film and the heat-sealable resin film are pasted, they can be laminated by a dry lamination method using an adhesive. The adhesive layer used in the present invention can use a general lamination adhesive. For example, a (non-)solvent type, water-based type, or hot-melt type adhesive with poly (ester) carbamate, polyester, polyamide, epoxy, poly (meth) acrylic acid, polyethylene imine, ethylene-(meth) acrylic acid, polyvinyl acetate, (modified) polyolefin, polybutadiene, wax, casein, etc. as the main component can be used. Among them, if heat resistance and flexibility that can follow the dimensional changes of each substrate are taken into consideration, carbamate or polyester are preferred. The adhesive layer can be laminated by direct gravure coating, reverse gravure coating, kiss coating, die coating, roll coating, dip coating, knife coating, spray coating, fountain coating, or other methods. In order to exhibit sufficient adhesion, the coating amount after drying is preferably 1 to 8 g / m 2More preferably, it is 2 to 7 g / m 2 , more preferably 3 to 6 g / m 2 If the coating amount is less than 1g / m 2 If the thickness exceeds 8g / m 2 If the above amount is exceeded, it will take time to completely cure the film, unreacted substances are likely to remain, and the adhesive force will decrease.
[0191] [Printing layer]
[0192] Furthermore, the packaging material of the present invention may have at least one printed layer laminated between the base film and the heat-sealable resin film or on the outside thereof.
[0193] As the printing ink for forming the printing layer, water-based and solvent-based resin-containing printing inks can be preferably used. Here, as the resin used in the printing ink, acrylic resins, urethane resins, polyester resins, vinyl chloride resins, vinyl acetate copolymer resins and mixtures thereof can be exemplified. The printing ink may contain known additives such as antistatic agents, light shielding agents, ultraviolet absorbers, plasticizers, lubricants, fillers, colorants, stabilizers, lubricants, defoamers, crosslinking agents, anti-blocking agents, antioxidants, etc. As the printing method for setting the printing layer, it is not particularly limited, and known printing methods such as offset printing, gravure printing, and screen printing can be used. The drying of the solvent after printing can use known drying methods such as hot air drying, hot roller drying, and infrared drying.
[0194] [Characteristics of packaging materials]
[0195] As the packaging material of the present invention, any conceivable laminated structure can be adopted. From the perspective of environmental burden, the structure obtained by pasting a substrate film having a barrier layer and a heat-sealable resin film has the least number of materials used / pasting steps, so it is preferred. On the other hand, as described above, from the perspective of improving toughness and gas barrier performance, for example, as one of the preferred structures, a laminate obtained by laminating a film laminated with a gas barrier layer by sandwiching a substrate film without a gas barrier layer and a thermoplastic copolymer having a heat-sealable resin layer can be listed. At this time, the following advantages can also be listed: by laminating the printed layer on the substrate film on the surface side, there is no need to print on the film having the gas barrier layer. In addition, pasting with a white substrate film or a heat-sealable resin film to improve shielding properties or pasting with an anti-ultraviolet film to achieve light-shielding properties is also one of the suitable structures.
[0196] In the packaging material of the present invention, the heating elongation at 130°C of at least one sheet of the base film peeled off from the above-mentioned material, measured by a thermomechanical analyzer, must be 6% or less in both the MD direction and the TD direction. Thus, the heat resistance required when used as a packaging body can be ensured. For example, a packaging body with good finishing when heat-sealed at a high temperature of 130°C or above, stable sealing strength, and less dimensional and appearance changes during severe wet heat treatment such as steaming can be made. The heating elongation in the MD direction and the TD direction at 130°C is preferably 5.5% or less, more preferably 5.0% or less, and further preferably 4.5% or less, and the lower limit is preferably 0%. When the heating elongation at 130°C is not within the above-mentioned range, the heat resistance as a packaging body is reduced, and as a result, poor appearance may occur during sealing and wet heat treatment. In the present invention, the heating elongation is a value measured by a thermomechanical analyzer (TMA) method, more specifically, based on the method described in the embodiments. By using the TMA method, it is possible to quantitatively determine the dimensional change caused by the thermal load under a predetermined tension. In addition, it is considered that the tension and heat in various processing scenarios can be arbitrarily set, and thus it becomes an index for confirming behavior similar to actual processing.
[0197] As described in the column [Base Film], in the present invention, in order to set the heating elongation of the base film peeled off from the packaging material to the aforementioned range, it is preferred to use a base film having a heating elongation of 10% or less in both the MD direction and the TD direction at 130°C. Furthermore, by subjecting the base film to post-heat treatment, the heating elongation can be reduced. As a means of heating treatment, it can be carried out by annealing the base film in a drying furnace, forming a gas barrier layer such as the aforementioned inorganic thin film layer (B), and applying heat in the anchor coating (C) / protective layer (D) coating process. As a heat application condition at this time, when heated, the surface temperature of the film is preferably 65°C or more, more preferably 70°C or more, and further preferably 75°C or more. Among them, if the film temperature reaches 90°C or more, it is possible that the expansion and contraction will become larger, resulting in reduced quality such as wrinkles, so the upper limit of heat application is 90°C.
[0198] By making the packaging material of the present invention have an oxygen permeability of 60 ml / m 2 ·d·MPa or less, thereby showing good gas barrier properties. Furthermore, by providing a barrier layer on each film, it can be preferably set to 50ml / m 2 ·d·MPa or less, more preferably 40ml / m 2 ·d·MPa or less. If the oxygen permeability exceeds 60ml / m 2On the other hand, the preferred lower limit of oxygen permeability is 0.5 ml / m 2 ·d·MPa or above. If the oxygen permeability is less than 0.5ml / m 2 ·d·MPa, the barrier performance is excellent, but the residual solvent may not easily permeate to the outside of the bag, and the amount of transfer to the content may increase relatively, which is not preferred.
[0199] From the viewpoint of exhibiting good gas barrier properties, the packaging material of the present invention preferably has an oxygen permeability of 60 ml / m2 under the conditions of 23°C x 65% RH after boiling at 95°C x 30 minutes or retorting at 120°C x 30 minutes. 2 Furthermore, by providing a barrier layer on each film, the pressure drop can be preferably set to 50 ml / m 2 ·d·MPa or less, more preferably 40ml / m 2 ·d·MPa or less. If the oxygen permeability exceeds 60ml / m 2 On the other hand, the preferred lower limit of oxygen permeability is 0.5 ml / m 2 ·d·MPa or above. If the oxygen permeability is less than 0.5ml / m 2 ·d·MPa, the barrier performance is excellent, but the residual solvent may not easily permeate to the outside of the bag, and the amount of transfer to the content may increase relatively, which is not preferred.
[0200] From the viewpoint of exhibiting good gas barrier properties, the water vapor permeability of the packaging material of the present invention under the conditions of 40°C × 90% RH is preferably 5.0 g / m 2 Furthermore, by providing a barrier layer on each film, the density can be preferably set to 4.0 g / m 2 ·d or less, more preferably 3.0 g / m 2 ·d or less. If the water vapor permeability exceeds 5.0g / m 2 On the other hand, the lower limit of water vapor permeability is preferably 0.1 g / m 2 ·d or more. If the water vapor permeability is less than 0.1g / m 2 , the barrier performance is excellent, but there is a possibility that the residual solvent is not easy to penetrate to the outside of the bag, and the amount transferred to the contents is relatively increased, so it is not preferred.
[0201] From the viewpoint of exhibiting good gas barrier properties, the water vapor permeability of the packaging material of the present invention at 40°C × 90% RH after boiling at 95°C × 30 minutes or retorting at 120°C × 30 minutes is preferably 5.0 g / m 2Furthermore, by providing a barrier layer on each film, the density can be preferably set to 4.0 g / m 2 ·d or less, more preferably 3.0 g / m 2 ·d or less. If the water vapor permeability exceeds 5.0g / m 2 On the other hand, the lower limit of water vapor permeability is preferably 0.1 g / m 2 ·d or more. If the water vapor permeability is less than 0.1g / m 2 , the barrier performance is excellent, but there is a possibility that the residual solvent is not easy to penetrate to the outside of the bag, and the amount transferred to the contents is relatively increased, so it is not preferred.
[0202] The packaging material of the present invention preferably needs to have a linear cutting property of 10 mm or less. Thus, when used as a packaging body, it is possible to ensure a preferred tearing property, which is preferred. The linear cutting property is preferably 9 mm or less, more preferably 8 mm or less, and further preferably 7 mm or less. When the linear cutting property is greater than 10 mm, undesirable situations such as poor separation may occur. Details of the method for measuring the linear cutting property are shown in the examples described below.
[0203] The packaging material of the present invention requires a ring stiffness value of 140mN / 25mm or more. Ring stiffness refers to: a ring is formed using a film cut into short strips of a specified size, and the rebound force of the ring is measured when the ring is squeezed only a specified amount in the radial direction. It is an indicator of the rigidity of the film. By setting the value of the ring stiffness to the above range, it is possible to ensure a preferred stiffness when used as a self-supporting packaging body, for example. The value of the ring stiffness is preferably 145mN / 25mm or more, more preferably 150mN / 25mm or more, and further preferably 155mN / 25mm or more. When the value of the ring stiffness is less than 140mN / 25mm, the self-support of the bag may be insufficient. The details of the method for measuring the ring stiffness are shown in the examples described below. The value of the ring stiffness can be achieved by adjusting the type and thickness of each film used in the laminated structure, especially the stiffness of the heat-sealable resin that occupies the main thickness ratio in the whole. As described in the [Heat-sealable resin film] column, the ring stiffness can be set to a predetermined value by adjusting the plane orientation coefficient of the heat-sealable resin. It can also be adjusted by the film thickness, but if a stiff feeling is desired, the thickness will be increased, which is not preferred from the perspective of volume reduction and may lead to cost increases.
[0204] The heat seal strength of the heat seal layer resin layers of the packaging material of the present invention when heat-sealed at a temperature of 160°C or 170°C, a sealing rod pressure of 0.2MPa, and a sealing time of 2 seconds is preferably 15N / 15mm or more. If the heat seal strength is less than 15N / 15mm, the sealed portion is easily peeled off, and therefore, it cannot be used in applications with a large amount of content, and its use as a packaging bag is limited. The heat seal strength is preferably 16N / 15mm or more, and more preferably 17N / 15mm or more.
[0205] The packaging material of the present invention preferably has an excellent appearance after heat sealing. Specifically, it is preferred that wrinkles do not gather at the sealed portion or the bag does not tilt. In order to maintain the appearance after sealing, the following methods can be cited: setting the heating elongation of the aforementioned base film to the aforementioned specified range and setting the heat shrinkage of the heat-sealable resin film to the aforementioned specified range.
[0206] As an evaluation criterion for the single materialization in the packaging material of the present invention, when the ratio of the thickness of the polyolefin raw material to the total thickness of each film and the adhesive is calculated as a single material (single material) ratio, the single material ratio is preferably 70% or more. It is more preferably 80% or more, and further preferably 90% or more. By setting the single material ratio to this range, a packaging material structure that is easily recycled can be made. If the single material ratio is less than 70%, it may be difficult to recycle due to foreign matter originating from different raw materials. It should be noted that, as described above, as the polyolefin resin constituting the base film, a polypropylene resin is preferably used. If a polypropylene resin is also used for the heat-sealing resin layer, a structure that is more easily recycled can be made. If all the polyolefin raw materials used are set to polypropylene resins, a structure that is further easily recycled can be made.
[0207] In the packaging material of the present invention, the total thickness of each film and adhesive is preferably 20 to 140 μm. It is more preferably 25 to 135 μm, and further preferably 30 to 130 μm. By setting the total thickness of the packaging material to this range, a packaging body that can exhibit the stiffness required as the aforementioned packaging material and further exhibit necessary physical properties such as toughness and barrier properties can be made, so it is preferred. If the total thickness is less than 20 μm, it is possible that the stiffness as a bag is insufficient and it will not be self-supporting. In addition, the toughness may be insufficient, and the bag may rupture or have holes. On the other hand, if the total thickness exceeds 140 μm, the stiffness becomes too strong and difficult to handle. In addition, it leads to an increase in the cost of the packaging body, which is not economically preferred.
[0208] The packaging material of the present invention has excellent heat resistance, straight cutting property, stiffness, barrier property, and visual recognition as described above, and can be used as various packaging bodies. Examples of packaging bodies include sterilization treatment by boiling or steaming, frozen food use, vacuum packaging use, microwave heating use, and the like.
[0209] The form of the package obtained by using the packaging material of the present invention is not particularly limited, and various forms can be adopted. Examples of the packaging form include three-sided / four-sided soft bags, self-supporting soft bags, and spouted soft bags.
[0210] The content filled in the packaging bag obtained by using the packaging material of the present invention is not particularly limited, and the content may be liquid, powder or gel. In addition, the content may be food or not.
[0211] Example
[0212] Next, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples. It should be noted that various evaluations were performed by the following measuring methods.
[0213] (1)Thickness of various films
[0214] The measurement was performed using a micrometer in accordance with JIS K7130-1999 A method.
[0215] (2) Composition / Thickness of Inorganic Thin Film Layer (B) on Substrate Film
[0216] The film thickness and composition of the laminated thin films (after film lamination) used in the examples and comparative examples were measured using a fluorescent X-ray analyzer ("supermini200" manufactured by Rigaku Corporation) using a pre-made calibration curve. It should be noted that the conditions for exciting the X-ray tube were 50 kV and 4.0 mA.
[0217] (3) Adhesion amount of cover layer (A) / anchor coating (C) / protective layer (D) on the substrate film
[0218] In each of the embodiments and comparative examples, each laminated film obtained at the stage where a predetermined covering layer (A) / anchor coating (C) / protective layer (D) is laminated on a base film is used as a sample, and a 100 mm × 100 mm test piece is cut out from the sample. The coating layer is wiped with any of water, ethanol or acetone, and the adhesion amount is calculated based on the change in the mass of the film before and after wiping.
[0219] (4) Method for evaluating the appearance of substrate film after processing
[0220] In each of the Examples and Comparative Examples, after laminating the cover layer (A) / inorganic thin film layer (B) / anchor coating layer (C) / protective layer (D), the film appearance was visually evaluated.
[0221] ○: No defects, good ×: Any defect such as wrinkles, uneven coating, or shrinkage cavities occurs
[0222] (5) Heating elongation of substrate film (%)
[0223] The heating elongation was measured for the substrate film used in each example / comparative example. The heating elongation was determined by TMA measurement using a thermomechanical analyzer ("TMA-60" manufactured by Shimadzu Corporation).
[0224] Regarding the heating elongation in the MD direction, the substrate films of the examples and comparative examples were used to prepare short strip samples with a width of 30 mm in the MD direction and 4 mm in the TD direction. Regarding the measurement conditions, the distance between the chucks was set to 10 mm, the measurement temperature range was set to 30°C to 150°C, the heating rate was set to 20°C / min, and the tensile load applied to the sample piece was set to 0.39 N. The heating elongation was calculated based on the distance between the chucks before heating (mm) and the distance between the chucks when the temperature reached 130°C (mm).
[0225] Regarding the heating elongation in the TD direction, the substrate films of the examples and comparative examples were used to prepare short strip samples with a width of 30 mm in the TD direction and 4 mm in the MD direction. Regarding the measurement conditions, the distance between the chucks was set to 10 mm, the measurement temperature range was set to 30°C to 150°C, the heating rate was set to 20°C / min, and the tensile load applied to the sample piece was set to 0.39 N. The heating elongation was calculated based on the distance between the chucks before heating (mm) and the distance between the chucks when the temperature reached 130°C (mm).
[0226] The heating elongation (S130) (%) at 130°C was determined by the following formula.
[0227] (S130) = (distance between chucks when heated to 130°C - distance between chucks before heating) / distance between chucks before heating × 100 (%)
[0228] (6) Evaluation method of dimensional change rate of substrate film after processing
[0229] In each of the examples and comparative examples, the length A in the film width direction before laminating the covering layer (A) / inorganic thin film layer (B) / anchor coating layer (C) / protective layer (D) and the length B in the film width direction after laminating (for example, when the anchor coating layer, the covering layer, the inorganic thin film layer, and the protective layer are all laminated, the length B is measured after laminating the protective layer), and the value X calculated according to the following formula is used as the dimensional change rate (%) after processing for evaluation.
[0230] Dimensional change rate after processing X = (AB) / A×100(%)
[0231] (7) Thermal shrinkage of heat-sealable resin film
[0232] In each embodiment and comparative example, the heat-sealable resin film was cut into 120 mm squares. Marking lines were drawn in the length direction and the width direction at intervals of 100 mm. The sample was suspended in an oven kept at 120°C and heat treated for 30 minutes. The distance between the marking lines was measured and the heat shrinkage was calculated according to the following formula. The measurement was performed with N=3 and the average value was calculated.
[0233] Thermal shrinkage rate = (line length before heat treatment - line length after heat treatment) / line length before heat treatment × 100 (%)
[0234] (8) Orientation coefficient in the longitudinal direction and plane orientation coefficient of heat-sealable resin film
[0235] In each example and comparative example, the density was evaluated according to JIS K0062:1999 Chemical products refractive index measurement method. The measurement was performed with N=3 and the average value was calculated. The orientation coefficient ΔNx in the longitudinal direction was calculated by Formula 1, and the orientation coefficient ΔP in the plane direction was calculated by Formula 2.
[0236] ΔNx=Nx-(Ny+Nz) / 2 (Formula 1)
[0237] ΔP=(Nx+Ny) / 2-Nz (Formula 2)
[0238] [Production of packaging materials]
[0239] (9) Preparation of packaging materials for evaluation
[0240] In the case of a single substrate film, a urethane two-component curing adhesive ("TAKELAC (registered trademark) A525S" and "TAKENATE (registered trademark) A50" manufactured by Mitsui Chemicals, Inc. are mixed in a ratio of 13.5:1 (mass ratio)) is applied to the substrate film described in the embodiments and comparative examples in such a manner that the thickness after drying at 80°C becomes 3 μm, and then various heat-sealable resin films described later are dry laminated on a metal roller heated to 60°C and aged at 40°C for 2 days (48 hours) to obtain a laminated stack for evaluation. On the other hand, in the case of two substrate films, a urethane two-component curing adhesive (Mitsui Chemicals, Inc. "TAKELAC (registered trademark) A525S" and "TAKENATE (registered trademark) A50" were mixed at a ratio of 13.5:1 (mass ratio)) was applied to the substrate film described in the Examples and Comparative Examples so that the thickness after drying treatment at 80°C was 3 μm, and the other substrate film was dry-laminated on a metal roll heated to 60°C and wound up to form a roll. After applying the same adhesive to the roll so that the thickness after drying treatment at 80°C was 3 μm, a heat-sealable resin film described later was dry-laminated on a metal roll heated to 60°C and aged at 40°C for 2 days (48 hours) to obtain a packaging material for evaluation.
[0241] (10) Evaluation method of oxygen permeability of packaging materials
[0242] The packaging material prepared in the above (9) was subjected to oxygen permeability measurement in accordance with JIS-K7126 B method using an oxygen permeability measuring device ("OX-TRAN (registered trademark) 2 / 22" manufactured by MOCON Co., Ltd.) at a temperature of 23°C and a humidity of 65% RH. It should be noted that the oxygen permeability measurement was conducted in the direction of oxygen permeation from the substrate film side of the packaging material to the heat-sealable resin layer side. On the other hand, the packaging material prepared in the above (9) was subjected to a boiling treatment in hot water at 95°C for 30 minutes or a steaming treatment in hot water at 120°C for 30 minutes, and dried at 40°C for 1 day (24 hours). For the obtained packaging material after the wet heat treatment, the oxygen permeability (after boiling, after steaming) was measured in the same manner as above. In Table 7, the oxygen permeability is expressed as "OTR", the oxygen permeability after boiling is expressed as "OTR after boiling", and the oxygen permeability after steaming is expressed as "OTR after steaming".
[0243] (11) Evaluation method of water vapor permeability of packaging materials
[0244] The water vapor permeability of the packaging material prepared in the above (9) was measured in accordance with JIS-K7129 B method using a water vapor permeability measuring device ("PERMATRAN-W 3 / 33MG" manufactured by MOCON) in an atmosphere of a temperature of 40°C and a humidity of 90% RH. It should be noted that the water vapor permeability was measured in the direction of water vapor permeating from the base film side of the packaging material toward the heat seal resin side. On the other hand, the packaging material prepared in the above (9) was subjected to a boiling treatment in hot water at 95°C for 30 minutes or a retorting treatment in hot water at 120°C for 30 minutes, and dried at 40°C for 1 day (24 hours). The water vapor permeability (after boiling, after retorting) of the obtained packaging material after the wet heat treatment was measured in the same manner as above. In Table 7, the water vapor permeability is expressed as "WVTR", the water vapor permeability after boiling is expressed as "WVTR after boiling", and the water vapor permeability after retorting is expressed as "WVTR after retorting".
[0245] (12) Evaluation method of heat seal strength of packaging materials
[0246] For the packaging material produced in (9) above, the heat seal strength is measured in accordance with JIS Z1707. The specific steps are shown. The heat seal covers of the sample are bonded to each other using a heat sealer. The heat seal conditions are as follows: the upper rod temperature is 160°C or 170°C, the lower rod temperature is 30°C, the pressure is 0.2MPa, and the time is 2 seconds. The bonded sample is cut out in such a way that the sealing width becomes 15mm. The peel strength is measured using a universal tensile testing machine "DSS-100" (manufactured by Shimadzu Corporation) at a tensile speed of 200mm / min. The peel strength is expressed as the strength per 15mm (N / 15mm). It should be noted that as an evaluation of the sealing appearance, the case where it can be sealed without wrinkles is set to 0, the case where wrinkles are generated in a part is set to △, and the case where wrinkles are generated on the entire surface is set to ×, and a relative evaluation is performed.
[0247] (13) Heating elongation of the base film peeled off from the packaging material (%)
[0248] The base film peeled off from the packaging material prepared in the above (9) was measured for elongation upon heating. The elongation upon heating was determined by TMA measurement using a thermomechanical analyzer ("TMA-60" manufactured by Shimadzu Corporation).
[0249] Regarding the heating elongation in the MD direction, the packaging materials of the examples and comparative examples were cut into strips with a width of 80 mm in the MD direction and 30 mm in the TD direction, and the base film peeled off between the adhesive layers was further cut into strips with a width of 30 mm in the MD direction and 4 mm in the TD direction to prepare samples. The measurement conditions were as follows: the distance between the chucks was 10 mm, the measurement temperature range was 30°C to 150°C, the heating rate was 20°C / min, and the tensile load applied to the sample piece was 0.39 N. The heating elongation was calculated based on the distance between the chucks before heating (mm) and the distance between the chucks when the temperature reached 130°C (mm).
[0250] Regarding the heating elongation in the TD direction, the packaging materials of the examples and comparative examples were cut into strips with a width of 80 mm in the TD direction and 30 mm in the MD direction, and the base film peeled off between the adhesive layers was further cut into strips with a width of 30 mm in the TD direction and 4 mm in the MD direction to prepare samples. The measurement conditions were as follows: the distance between the chucks was 10 mm, the measurement temperature range was 30°C to 150°C, the heating rate was 20°C / min, and the tensile load applied to the sample piece was 0.39 N. The heating elongation was calculated based on the distance between the chucks before heating (mm) and the distance between the chucks when the temperature reached 130°C (mm).
[0251] The heating elongation (S130) (%) at 130°C was determined by the following formula.
[0252] (S130) = (distance between chucks when heated to 130°C - distance between chucks before heating) / distance between chucks before heating × 100 (%)
[0253] (14) Evaluation criteria for single material: Single material ratio
[0254] For the packaging material produced in (9) above, as a standard for evaluating the single material, the ratio of the thickness of the olefin-based raw material to the total thickness of each film and the adhesive was calculated as the single material ratio.
[0255] (15) Visual recognition / evaluation criteria for microwave oven suitability
[0256] For the packaging material produced in (9) above, as an evaluation criterion for visual recognition / microwave oven suitability, the case where the packaging body is transparent and the barrier layer does not use aluminum foil or aluminum vapor deposition is set to 0.
[0257] (16) Linear cutting properties of packaging materials
[0258] The packaging material prepared in (9) above was evaluated for linear cutting properties. Linear cutting properties refer to the ability to tear the laminate in a straight line parallel to one direction when the laminate is torn. The measurement was performed by the following method. In the examples and comparative examples, in order to demonstrate the linear cutting properties along the stretching direction, the measurement was performed along the stretching direction. The laminate was cut into short strips with a length of 150 mm in the stretching direction and a length of 60 mm in the direction perpendicular to the measuring direction, and a 30 mm cut was made from the center of the short side along the measuring direction. According to JIS K7128-1:1998, the sample was torn at a test speed of 200 mm / min±10%. At the moment when 120 mm was torn along the stretching direction without a 30 mm cut, the distance moved in the direction perpendicular to the stretching direction was measured and its absolute value was recorded. For both the case where the relative right side slice was clamped by the upper clamp and the case where the relative left side slice was clamped by the upper clamp, the measurement was performed with N=3 each, and the respective average values were calculated. The measurement result with the larger value between the measurement results on the right and left sides was adopted.
[0259] (17) Ring stiffness of packaging materials
[0260] The ring stiffness of the packaging material produced in (9) above is measured. It is cut into short strips of film with a width of 25 mm and a length of 110 mm, so that the length direction of the short strips of film is consistent with the direction of the measured object. The cut short strips of film are placed in a ring stiffness tester manufactured by Toyo Seiki Seisaku-sho Co., Ltd. to measure the rebound force. The measurement frequency is set to 50 Hz. The rebound force value (mN / 25 mm) obtained by the measurement is set as the value of the ring stiffness.
[0261] The substrate films used in the present example and the comparative example are described below. It should be noted that the substrate films used in Examples 1 to 11 and Comparative Examples 1 to 8 are shown in Table 6.
[0262] [Production of substrate film]
[0263] Tables 1 to 4 show the details of the polypropylene resin raw materials used in the production of the polyolefin substrate films OPP-1 to 5, the film production conditions, and the raw material blending ratios.
[0264] [Table 1]
[0265]
[0266] [Table 2]
[0267]
[0268] [Table 3]
[0269] Film Forming Conditions a b C Molten resin temperature (℃) 250 250 250 Cooling roller temperature (℃) 40 30 30 Longitudinal stretching ratio (times) 4.5 4.5 4.5 Longitudinal stretching temperature (℃) 125 125 125 Stretching ratio in width direction (times) 8.2 8.2 8.2 Width direction stretching preheating temperature (℃) 174 168 168 Stretching temperature in width direction (℃) 158 155 162 Heat fixation temperature (℃) 175 165 165 Relaxation rate in width direction (%) 6.7 6.7 0
[0270] [Table 4]
[0271]
[0272] (OPP-1)
[0273] The substrate layer (A) was prepared by blending a propylene homopolymer (PP “FS2012” manufactured by Sumitomo Chemical Co., Ltd.: comonomer content: 0 mol %; hereinafter referred to as “PP-2”) having Mn=81,000, Mw=320,000, MFR=2.2 g / 10 min, and meso pentad content [mmmm]=99.2% as shown in Table 1 at a ratio of 30 mass % and a propylene homopolymer (PP “FLX80E4” manufactured by Sumitomo Chemical Co., Ltd.: comonomer content: 0 mol %; hereinafter referred to as “PP-3”) having Mn=65,000, Mw=240,000, MFR=7.5 g / 10 min, and meso pentad content [mmmm]=98.9% at a ratio of 70 mass %.
[0274] In addition, the surface layer (B) used a propylene polymer having Mn=55,000, Mw=300,000, and MFR=5.6 g / 10 minutes (NOVATEC (registered trademark) PP "FL4" manufactured by Japan Polypropylene Co., Ltd.: abbreviated as "PP-5") at a ratio of 24.8 mass%, a propylene polymer having Mn=59,000, Mw=310,000, and MFR=3.2 g / 10 minutes (Prime Polymer Co., Ltd., Prime Polypro "F-300SP": abbreviated as "PP-6") at a ratio of 72.2 mass%, and a master batch A shown in Table 2 at a ratio of 3.0 mass%.
[0275] The base layer (A) was extruded by a 45 mm extruder, the surface layer (B) was extruded by a 25 mm extruder, and the surface layer (C) (the composition was the same as that of the surface layer (B)) was extruded by a 20 mm extruder. The raw resins were melted at 250°C, coextruded from a T die into a sheet, and cooled and solidified in such a way that the surface layer (B) contacted a cooling roll at 40°C, and then stretched to 4.5 times in the longitudinal direction (MD) at 125°C. Then, in a tenter, both ends of the film in the width direction (TD) were clamped with a clamp, preheated at 174°C, stretched to 8.2 times in the width direction (TD) at 158°C, and relaxed by 6.7% in the width direction (TD) while heat fixing was performed at 175°C. The film-forming conditions at this time were referred to as film-forming conditions a.
[0276] In this manner, a biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained.
[0277] The surface of the surface layer (B) of the biaxially oriented polypropylene film was subjected to corona treatment using a corona treatment machine manufactured by SOFTAL Corona & Plasma GmbH under the condition of applying a current value of 0.75 A, and then wound up using a winder. The thickness of the obtained film was 20 μm (the thickness of the surface layer (B) / substrate layer (A) / surface layer (C) was 1.0 μm / 18.0 μm / 1.0 μm). The details of this composition are shown in Table 4.
[0278] (OPP-2)
[0279] The substrate layer (A) used 100 mass% of a propylene homopolymer (manufactured by Japan Polypropylene Co., Ltd., PP "FL203D": comonomer content 0 mol%; hereinafter referred to as "PP-1") having Mn = 56,000, Mw = 310,000, MFR = 2.5 g / 10 minutes, and meso pentad fraction [mmmm] = 94.8% as shown in Table 1, and the surface layer (B) was blended with 95.2 mass% of PP-1 and 4.8 mass% of master batch B, and the surface layer (C) was blended with 93.6 mass% of PP-1 and 6.4 mass% of master batch B. In addition, the film was formed under the conditions b of Table 3, and the same conditions as OPP1 were used except that the film was formed to obtain a 20 μm biaxially oriented polypropylene film. The details of this constitution are shown in Table 4.
[0280] (OPP-3)
[0281] The substrate layer (A) contains 27.0% by mass of the polypropylene homopolymer PP-2 shown in Table 1, 70.0% by mass of the polypropylene homopolymer PP-3 shown in Table 1, and ethylene homopolymer (PE-1) ("SLH218" manufactured by Braskem, MFR: 2.3 g / 10 min, melting point: 126°C, biobased content: 84%, density: 0.916 g / cm 3 The same conditions as those of OPP1 were adopted except that the ratio of ) was 3% by mass, to obtain a 20 μm biaxially oriented polypropylene film. The details of this constitution are shown in Table 4.
[0282] (OPP-4)
[0283] The surface layer (B) was mixed with 96.0% by mass of PP-6 and 4.0% by mass of master batch A, and the surface layer (C) was mixed with 52.0% by mass of a propylene-ethylene copolymer (WINTEC (registered trademark) PP "WFX4M" manufactured by Japan Polypropylene Co., Ltd.: abbreviated as "PP-4") having Mn=80,000, Mw=220,000, and MFR=7.0 g / 10 minutes as shown in Table 1, 45.0% by mass of PP-6, and 3.0% by mass of the master batch A shown in Table 2. The same conditions as those of OPP1 were used to obtain a 20 μm biaxially oriented polypropylene film. The details of this constitution are shown in Table 4.
[0284] (OPP-5)
[0285] In the surface layer (B), PP-6 was blended at a ratio of 96.4 mass % and master batch A was blended at a ratio of 3.6 mass %; in the surface layer (C), PP-6 was blended at a ratio of 94.0 mass % and master batch A was blended at a ratio of 6.0 mass %, and the stretching conditions were changed to the conditions c described in Table 3. A biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained by the same method as OPP-1, except that the stretching conditions were changed to the conditions c described in Table 3. The details of this structure are shown in Table 4.
[0286] (Other substrate films)
[0287] NY: Biaxially stretched polyamide film (manufactured by Toyobo Co., Ltd., N1100-15μm)
[0288] Vapor-deposited PET: 12 μm thick transparent vapor-deposited polyester film ("VE707" manufactured by Toyobo Co., Ltd.)
[0289] (Cover layer (A))
[0290] The coating liquid for forming the covering layer (A) used in the present example and the comparative example is described below in detail.
[0291] [Polyvinyl alcohol resin (a)]
[0292] 10 parts by mass of a completely saponified polyvinyl alcohol resin (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name: G POLYMER OKS8049Q, (saponification degree of 99.0% or more, average degree of polymerization of 450)) was added to 90 parts by mass of purified water, and heated to 80°C while stirring, and then stirred for about 1 hour. Thereafter, the mixture was cooled to room temperature, thereby obtaining a substantially transparent polyvinyl alcohol solution (PVA solution) (a) having a solid content of 10%.
[0293] [Inorganic layered compound dispersion (b)]
[0294] 5 parts by mass of montmorillonite (trade name: KUNIPIA F, manufactured by KUNIMINE INDUSTRIES CO., LTD.) as an inorganic layered compound was added to 95 parts by mass of purified water while stirring, and fully dispersed using a homogenizer at 1500 rpm. Thereafter, the mixture was kept at 23° C. for 1 day to obtain an inorganic layered compound dispersion (b) having a solid content of 5%.
[0295] [Coating liquid 1 used in cover layer 1 (cover 1)]
[0296] The respective materials were mixed at the following blending ratio to prepare a coating liquid (resin composition for a cover layer).
[0297]
[0298] [Coating liquid 2 used in cover layer 2 (cover 2)]
[0299] The respective materials were mixed at the following blending ratio to prepare a coating liquid (resin composition for a cover layer).
[0300] Ion exchange water 15.00 mass%
[0301] Isopropyl alcohol 15.00 mass%
[0302] Polyvinyl alcohol resin (a) 70.00 mass%
[0303] (Coating of coating liquid on film (lamination of cover layer))
[0304] The coating solution prepared above was applied to the corona treated surface of the substrate film by gravure roll coating, pre-dried at 90°C for 4 seconds, and then dried at 120°C for 4 seconds to obtain a covering layer. The adhesion amount of the covering layer at this time was 0.30 g / m 2 Thereafter, a post-heat treatment was performed at 40° C. for 2 days (48 hours). As described above, a laminated film having either the cover layer 1 or 2 was produced.
[0305] (Inorganic thin film layer (B))
[0306] The following describes the method for producing the inorganic thin film layer (B) used in each example and comparative example. It should be noted that the inorganic thin film layer (B) used in Examples 2 to 11 and Comparative Examples 1 to 3, 5, and 8 is shown in Table 6.
[0307] (Formation of Inorganic Thin Film Layer 1)
[0308] As the inorganic thin film layer 1 (evaporation 1), a composite oxide layer of silicon dioxide and aluminum oxide is formed on the substrate film or the anchor coating layer by electron beam evaporation. As the evaporation source, granular SiO2 (purity 99.9%) and Al2O3 (purity 99.9%) of about 3 mm to 5 mm are used. The film thickness of the inorganic thin film layer (SiO2 / Al2O3 composite oxide layer) in the thin film (thin film containing inorganic thin film layer / covering layer) obtained by the above operation is 13 nm. In addition, the composition of the composite oxide layer is SiO2 / Al2O3 (mass ratio) = 70 / 30.
[0309] (Formation of Inorganic Thin Film Layer 2)
[0310] As the inorganic thin film layer 2 (evaporation 2), silicon oxide was vapor-deposited on the substrate film or the anchor coat layer. A small vacuum vapor deposition apparatus (VWR-400 / ERH manufactured by ULVAC KIKO, Inc.) was used and the pressure was reduced to 10 -3 Pa or less, silicon monoxide was placed on a vapor deposition source B-110 manufactured by The Nilaco Corporation from the bottom of the substrate and heated to evaporate, thereby forming a silicon oxide film with a thickness of 30 nm on the thin film.
[0311] (Formation of Inorganic Thin Film Layer 3)
[0312] As the inorganic thin film layer 3 (evaporation 3), metal aluminum was vapor-deposited on the substrate film or the anchor coating layer. A small vacuum vapor deposition device (VWR-400 / ERH manufactured by ULVAC KIKO, Inc.) was used and the pressure was reduced to 10 -3 Pa or less, an aluminum foil with a purity of 99.9% was placed on a vapor deposition source CF-305W manufactured by The Nilaco Corporation from the bottom of the substrate, and the metal aluminum was heated and evaporated to form a metal aluminum film with a thickness of 30 nm on the thin film.
[0313] (Anchor coating (C))
[0314] The method for producing the anchor coating layer (C) used in each of the Examples and Comparative Examples is described below.
[0315] [Polyester resin (a)]
[0316] As the polyester component, polyester polyol ("DF-COAT GEC-004C" manufactured by DIC Corporation: solid content: 30%) was used.
[0317] [Polyisocyanate crosslinking agent (b)]
[0318] As the polyisocyanate component, a trimethylolpropane adduct of meta-xylylene diisocyanate ("TAKENATE D-110N" manufactured by Mitsui Chemicals, Inc.: solid content: 75%) was used.
[0319] [Silane coupling agent (c)]
[0320] As a silane coupling agent, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane ("KBM-603" manufactured by Shin-Etsu Chemical Co., Ltd.) was used.
[0321] [Urethane resin (d)]
[0322] As the urethane resin, a dispersion of a polyester urethane resin ("TAKELAC (registered trademark) WPB341" manufactured by Mitsui Chemicals, Inc.; solid content: 30%) was used.
[0323] [Coating liquid 1 for anchor coating-1]
[0324] A solution (15% by mass) obtained by dissolving a silane coupling agent (c) in acetone and an isocyanate (b) were mixed at the following ratio and stirred for 10 minutes using a magnetic stirrer. The resulting prepared solution was diluted with methyl ethyl ketone and 1-methoxy-2-propanol (hereinafter referred to as PGM), and a polyester resin (a) was further added to obtain the target coating solution 1. The mixing ratio is as follows.
[0325]
[0326] [Coating liquid 2 for anchor coating-2]
[0327] The following coating materials were mixed to prepare coating solution 2.
[0328] Water 46.00 mass%
[0329] Isopropyl alcohol 30.00 mass%
[0330] Urethane resin (d) 24.00 mass%
[0331] (Coating of coating liquid on film (Lamination of anchor coating layer))
[0332] The coating solution 1 or 2 was applied onto the corona treated surface of the substrate film by gravure roll coating, and then pre-dried at 95°C for 4 seconds and then mainly dried at 115°C for 4 seconds to obtain an anchor coating. The adhesion amount of the anchor coating (AC-1 to 3) was 0.40 g / m 2 Thereafter, a post-heat treatment was performed at 40° C. for 4 days (96 hours) to obtain the target laminated thin film.
[0333] (Protective layer (D))
[0334] [Coating liquid 1 used in protective layer (D)]
[0335] To a 5 mass % aqueous solution of a polyvinyl alcohol resin (PVA) having a saponification degree of 99% and a polymerization degree of 2400, a solution obtained by hydrolyzing tetraethoxysilane with 0.02 mol / L hydrochloric acid was added in a ratio of SiO2 / PVA=60 / 40 by mass as a gas barrier protective layer solution (coating solution 1).
[0336] (Coating of coating liquid on film (lamination of protective layer))
[0337] The coating liquid 1 was applied onto the inorganic thin film layer (B) of the substrate film by gravure roll coating, and dried in a dry oven at 120° C. for 10 seconds to obtain a protective layer 1. The adhesion amount of the protective layer at this time was 0.30 g / m 2 Thereafter, a post-heat treatment was performed at 40° C. for 2 days (48 hours). In the above manner, a laminated film having a protective layer was produced.
[0338] [Preparation of heat-sealable resin film CPP1]
[0339] 8.3 parts by mass of ethylene-butene copolymer elastomer resin (Tafmer A-4070S, Mitsui Chemicals, Inc.) having an MFR of 3.6 g / 10 min at 190°C and 2.16 kg and 2.8 parts by mass of propylene-butene copolymer elastomer resin (Tafmer XM-7070S, Mitsui Chemicals, Inc.) having an MFR of 3.0 g / 10 min at 190°C and 2.16 kg were prepared with respect to 100 parts by mass of propylene-ethylene random copolymer (WF577PG, Sumitomo Chemical Co., Ltd.) having an MFR of 3.2 g / 10 min at 230°C and 2.16 kg and a melting point of 142°C. The above-mentioned mixture was made into 100 parts by mass, 320 ppm of erucamide was added as an organic lubricant, and silica having an average particle size of 4 μm as an inorganic anti-blocking agent was added so that the content thereof in the resin composition became 2400 ppm. These raw materials are mixed uniformly to obtain a mixed raw material for producing a polyolefin resin film, and the obtained mixed material is used as a mixed raw material for a laminating layer, an intermediate layer, and a heat-sealing layer, respectively.
[0340] (Melt Extrusion)
[0341] The mixed raw material used in the middle layer uses a three-stage single screw extruder with a screw diameter of 90mm. The mixed raw material for the laminated layer and the mixed raw material for the heat-sealing layer use three-stage single screw extruders with diameters of 45mm and 65mm, respectively, and are introduced in the form of laminated layer / intermediate layer / heat-sealing layer in sequence, and introduced into a T-slit die. The die is designed as follows: the width is set to 800mm and the preforming is set to two stages, and the shape of the height difference part is set to a curve to make the flow path of the molten resin uniform, so that the flow path in the mold is uniform, and extrusion is performed under the condition of a mold outlet temperature of 230°C. The thickness ratios of the laminated layer / intermediate layer / heat-sealing layer are set to 25% / 50% / 25%, respectively. The laminated layer, the intermediate layer, and the heat-sealing layer are all similarly charged with the aforementioned mixed raw materials.
[0342] (cool down)
[0343] The molten resin sheet from the mold is cooled by a cooling roller at 21°C to obtain an unstretched polyolefin resin film with a thickness of 270 μm. When cooling by the cooling roller, the two ends of the film on the cooling roller are fixed by an air nozzle, and the full width of the molten resin sheet is pressed to the cooling roller by an air knife, while the vacuum chamber is activated to prevent air from being sandwiched between the molten resin sheet and the cooling roller. Both ends of the air nozzle are arranged in series along the direction of film travel. The mold is surrounded by sheets so that the wind cannot blow the molten resin sheet.
[0344] (Preheating)
[0345] The unstretched sheet was guided to a heated roller group and the sheet was preheated by contacting the rollers. The temperature of the preheating rollers was set to 105° C. Both sides of the film were preheated using a plurality of rollers.
[0346] (Vertical stretch)
[0347] The unstretched sheet was guided to a longitudinal stretching machine and stretched to 4.5 times by roller speed difference to a thickness of 60 μm. The temperature of the stretching rollers was set to 105°C.
[0348] (Annealing treatment)
[0349] The film was heat treated at 120° C. using an annealing roll while giving a relaxation rate of 5%. Both surfaces of the film were heat treated using a plurality of rolls.
[0350] (Corona treatment)
[0351] One side (laminated side) of the film was subjected to corona treatment.
[0352] (Coiling)
[0353] The film forming speed was 20 m / min. The film was trimmed and rolled up. The wetting tension on one side (laminated side) of the film was 42 mN / m.
[0354] Heat-sealable resin films of CPP2 to 6 were prepared in the same manner as shown in Table 5. In Table 5, Tafmer P0480 manufactured by Mitsui Chemicals, Inc. was used as the propylene ethylene block, and EP3721 manufactured by Sumitomo Chemical Co., Ltd. was used as the ethylene propylene copolymer elastomer.
[0355] [Table 5]
[0356]
[0357] As described above, a packaging material is produced which includes a cover layer (A), an anchor coating layer (C), an inorganic thin film layer (B), or a protective layer (D) on each film, and further has a heat-sealable resin film.
[0358] In each embodiment and comparative example, each packaging body was used and pasted by dry lamination using the above-mentioned adhesive to prepare a packaging material having the structure described in Table 6. It should be noted that in Table 6, in Example 9 and Comparative Example 7, two substrate films were used, and the upper section of each represents the first substrate film, and the lower section represents the second substrate film.
[0359] [Table 6]
[0360]
[0361] In addition, various evaluations were performed on the obtained packaging body. The results are shown in Table 7. In addition, in Table 7, "delamination" in Example 7 means delamination.
[0362] [Table 7]
[0363]
[0364] Industrial Applicability
[0365] The present invention can provide a packaging material, which can significantly improve the gas barrier performance by laminating a prescribed gas barrier layer that matches the required performance on a base film to form a laminated film, and further, by controlling the heating elongation of the aforementioned laminated film, it is possible to ensure heat resistance for various processing and sterilization treatments, and finally, by pasting a resin layer having excellent straight-line cutting properties and a strong stiffness as a heat-sealable resin film to the aforementioned base film, it is environmentally friendly and convenient. Moreover, the packaging material of the present invention has few processing steps and can be easily manufactured, so it is excellent in both economy and production stability, and can provide a gas barrier packaging body with uniform characteristics.
Claims
1. A packaging material, characterized in that: The invention comprises a heat-sealable resin film and at least one substrate film having a polyolefin resin as a constituent component. At least one of the substrate films is a laminated substrate film having a gas barrier layer, At least one of the substrate films peeled off from the packaging material has a heating elongation at 130° C. measured by a thermomechanical analyzer in both the MD direction and the TD direction of 6% or less. The packaging material has a linear cutting property of less than 10 mm in the MD direction or the TD direction, and a ring stiffness value of more than 140 mN / 25 mm, The oxygen permeability of the packaging material under 23°C×65%RH environment is 60ml / m 2 ·d·MPa or less.
2. The packaging material according to claim 1, characterized in that: The heat-sealable resin film comprises a propylene-α-olefin random copolymer and further comprises at least one component selected from the group consisting of an ethylene-propylene copolymer elastomer, an ethylene-butene copolymer elastomer, and a propylene-butene copolymer elastomer.
3. The packaging material according to claim 1, characterized in that: The gas barrier layer is an inorganic thin film layer formed of a material selected from the group consisting of aluminum, aluminum oxide, silicon oxide, and a composite oxide of silicon oxide and aluminum oxide.
4. The packaging material according to claim 1, characterized in that: The gas barrier layer is a covering layer including, as a constituent component, a resin selected from the group consisting of polyvinyl alcohol resins, polyester resins, and polyurethane resins.
5. The packaging material according to claim 1, characterized in that: An anchor coating layer is laminated between the base film and the gas barrier layer.
6. The packaging material according to claim 1, characterized in that: A protective layer is laminated on the gas barrier layer.
7. The packaging material according to claim 1, characterized in that: Two or more of the base films are used.
8. The packaging material according to claim 1, characterized in that: The polyolefin resin constituting the substrate film contains 1% by mass or more and 25% by mass or less of a plant-derived polyethylene resin.
9. The packaging material according to claim 1, characterized in that: For boiling or steaming purposes.
10. The packaging material according to claim 1, characterized in that For microwave heating purposes.
11. A packaging bag, comprising the packaging material according to any one of claims 1 to 10. 12 . A package body, wherein an object to be packaged is packaged using the packaging material according to any one of claims 1 to 10 or the packaging bag according to claim 11.
Citation Information
Patent Citations
Composite film and production thereof
JP1992359033A
Laminate and its manufacture
JP2000052501A
Body warmer packaging film
JP2003231221A
Polyester film for sealant, laminate and package
JP2017165059A
Laminated polypropylene film
WO2017221781A1